Optical laminate with protective film, polarizing plate with protective film, and image display device

CN122690729APending Publication Date: 2026-09-04SUMITOMO CHEM CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202610240138.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2026-01-16
Filing Date
2026-02-28
Publication Date
2026-09-04

AI Technical Summary

Technical Problem

[0002]通常,就平面转换(IPS)方式的液晶显示装置而言,已知在以相对于偏光片的吸收轴成45度的角度从倾斜方向进行视觉辨认的情况下,黑色显示的漏光较大,容易发生对比度的下降、色移

Benefits of technology

根据本发明,能够提供从倾斜方向进行视觉辨认时的漏光被减轻、并且保存稳定性优异的带保护膜的光学层叠体、带保护膜的偏光板、及具有具备偏光膜和前述光学层叠体的偏光板的图像显示装置。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122690729A_ABST
    Figure CN122690729A_ABST
Patent Text Reader

Abstract

The present application relates to an optical laminate with a protective film, a polarizing plate with a protective film, and an image display device. Provided are an optical laminate with a protective film, a polarizing plate with a protective film, and an image display device having a polarizing film provided with a polarizing plate with a protective film and the aforementioned optical laminate. An optical laminate with a protective film provided with a protective film and an optical laminate having a first optically anisotropic layer and a second optically anisotropic layer, the R40(550) of the optical laminate satisfies 110 nm ≤ R40(550) ≤ 175 nm, and the ratio of the tensile elastic modulus E1 in the direction parallel to the MD direction of the optical laminate to the tensile elastic modulus E2 in the direction parallel to the MD direction of the protective film satisfies E1 / E2 < 10.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to optical laminates with protective films, polarizing plates with protective films, and image display devices. Background Technology

[0002] Generally, in in-plane switching (IPS) liquid crystal display devices, it is known that when viewed from an angle of 45 degrees relative to the absorption axis of the polarizer, black displays exhibit significant light leakage, leading to a decrease in contrast and color shift. This phenomenon occurs because the angle between the absorption axes of the polarizers located on the front and back sides of the liquid crystal cell does not appear to reach 90 degrees.

[0003] To reduce light leakage during visual recognition from an inclined direction, a method has been proposed to arrange a phase retardation film between the liquid crystal cell and the polarizer. For example, Patent Document 1 describes a method to reduce light leakage in an IPS-type liquid crystal display device by arranging a stretched phase retardation film with refractive index anisotropy of nx>ny>nz and a stretched phase retardation film with refractive index anisotropy of nz>nx>ny.

[0004] Existing technical documents Patent documents Patent Document 1: Japanese Patent Application Publication No. 2009-139747 Summary of the Invention

[0005] The problem that the invention aims to solve For a laminate obtained by stacking multiple stretch phase difference films as described in Patent Document 1, when stored in a wound form, there may be wrinkles or defects in the film due to tight winding.

[0006] The purpose of this invention is to provide a new solution to the above-mentioned problems, namely, to provide an optical laminate with a protective film that has excellent preservation stability, a polarizing plate with a protective film, and an image display device having a polarizing plate having a polarizing film and the aforementioned optical laminate.

[0007] Methods for solving problems The inventors of this application conducted in-depth research to solve the aforementioned problems, resulting in the completion of this invention. Specifically, this invention includes the following aspects.

[0008] [1] An optical laminate with a protective film, comprising a protective film and an optical laminate having a first optical anisotropic layer and a second optical anisotropic layer. The R40(550) of the optical laminate satisfies 110nm ≤ R40(550) ≤ 175nm. The ratio of the tensile elastic modulus E1 of the optical laminate in the direction parallel to the MD direction to the tensile elastic modulus E2 of the protective film in the direction parallel to the MD direction satisfies E1 / E2<10.

[0009] [Where, R40 (550) represents the phase difference when the optical laminate is tilted by 40 degrees with an axis parallel to the fast axis in the plane of the optical laminate as the tilt center axis at a wavelength of 550 nm.] [2] The optical laminate with protective film as described in [1] above, wherein the thickness of the first optical anisotropic layer is more than 0.1 μm and less than 3.0 μm.

[0010] [3] An optical laminate with a protective film as described above [1], wherein the first optical anisotropic layer satisfies the following formula (1).

[0011] nx≈ny<nz (1) [In equation (1), nx represents the principal refractive index in the direction parallel to the film plane in the refractive index ellipsoid formed by the optical anisotropic layer; ny represents the principal refractive index in the direction parallel to the film plane and orthogonal to the direction of nx in the refractive index ellipsoid formed by the optical anisotropic layer; nz represents the principal refractive index in the direction perpendicular to the film plane in the refractive index ellipsoid formed by the optical anisotropic layer; where nx, ny, and nz each represent the principal refractive index relative to light with a wavelength of 550 nm.] [4] An optical laminate with a protective film as described above [1], wherein the first optical anisotropic layer satisfies the following formula (2).

[0012] 5nm≤R'40(550)≤30nm (2) [In equation (2), R'40 (550) represents the phase difference when the first optical anisotropic layer is tilted by 40 degrees at a wavelength of 550 nm.] [5] An optical laminate with a protective film as described above [1], wherein the first optical anisotropic layer satisfies the following formula (3).

[0013] R'40 (450) / R'40 (550) ≤ 1.04 (3) [In equation (3), R'40 (450) represents the phase difference when the first optical anisotropic layer is tilted by 40 degrees at a wavelength of 450 nm, and R'40 (550) represents the phase difference when the first optical anisotropic layer is tilted by 40 degrees at a wavelength of 550 nm.] [6] A polarizing plate with a protective film, comprising a polarizing film and an optical laminate with a protective film as described in any one of [1] to [5] above.

[0014] [7] A polarizing plate having the aforementioned polarizing film and the aforementioned optical laminate of the polarizing plate with protective film described in [6].

[0015] [8] An image display device comprising the polarizing plate described above [7].

[0016] Invention Effects According to the present invention, an optical laminate with a protective film is provided, which reduces light leakage when visually recognizing from an oblique direction and maintains excellent stability; a polarizing plate with a protective film is provided; and an image display device having a polarizing plate having a polarizing film and the aforementioned optical laminate is provided. Attached Figure Description

[0017] Figure 1 A schematic cross-sectional view showing an example of the layer composition of an optical laminate with a protective film.

[0018] Figure 2 A schematic cross-sectional view showing an example of the layer composition of an optical laminate with a protective film.

[0019] Figure 3 A schematic cross-sectional view illustrating an example of a method for manufacturing an optical laminate with a protective film.

[0020] Figure 4 A schematic cross-sectional view showing an example of the layered structure of a polarizing plate with a protective film.

[0021] Figure 5 A schematic cross-sectional view showing an example of the layered structure of a polarizing plate with a protective film.

[0022] Explanation of reference numerals in the attached figures 1: Optical laminate with protective film 2: Optical laminate 3: Protective film 4: First optical anisotropy layer 5: Second optical anisotropy layer 6: Laminating roller 7: Polarizing film 8: Polarizing plate with protective film Detailed Implementation

[0023] The following is based on Figure 1 and Figure 2 The optical laminate with a protective film of the present invention will be described, but the present invention is not limited to these methods.

[0024] like Figure 1As shown, the optical laminate 1 with a protective film of the present invention includes an optical laminate 2 and a protective film 3. Furthermore, the aforementioned optical laminate 2 has a first optical anisotropic layer 4 and a second optical anisotropic layer 5. The aforementioned protective film 3 can be laminated on the surface of the second optical anisotropic layer 5 in the aforementioned optical laminate 2 that is opposite to the first optical anisotropic layer 4, or it can be as follows: Figure 2 The first optical anisotropic layer 4, which is stacked in the optical laminate 2, is on the side opposite to the second optical anisotropic layer 5.

[0025] Furthermore, in this invention, the R40 (550) of the aforementioned optical stack preferably satisfies 110nm ≤ R40 (550) ≤ 175nm, more preferably 113nm ≤ R40 (550) ≤ 165nm, and even more preferably 117nm ≤ R40 (550) ≤ 160nm. Here, R40 (550) represents the phase difference value when the optical stack is tilted 40 degrees with an axis parallel to the fast axis direction within the plane of the optical stack as the tilt center axis at a wavelength of 550nm. By satisfying the above numerical range, when the optical stack is used in an image display device, light leakage and color shift can be prevented when visually recognizing the image from a tilted direction during black display.

[0026] In this invention, the term "MD direction" refers to the direction of travel when the optical laminate and protective film of this invention are transported in a long strip shape (i.e., the direction parallel to the direction of transporting the optical laminate and protective film), and the term "TD direction" refers to the direction orthogonal to the aforementioned direction of travel (i.e., the direction orthogonal to the direction of transporting the optical laminate and protective film, the width direction).

[0027] [Protective film] A protective film is a film used to protect the surface of an optical laminate. It is usually attached to the surface of the optical laminate by an adhesive layer or the like, and can be peeled off and removed along with the adhesive layer as needed. Therefore, the protective film can be peelably attached to the side of the first optical anisotropic layer opposite to the side of the second optical anisotropic layer, or the side of the second optical anisotropic layer opposite to the side of the first optical anisotropic layer, in an optical laminate.

[0028] The protective film can consist of a substrate film and an adhesive layer laminated on top of it.

[0029] The substrate film can be composed of thermoplastic resins, such as polyethylene resins, polypropylene resins, cyclic polyolefin resins, and other polyolefin resins; polyester resins such as polyethylene terephthalate and polyethylene naphthalate; polycarbonate resins; and (meth)acrylic resins. The substrate film can be a single-layer structure or a multi-layer structure.

[0030] From the viewpoint of obtaining excellent storage stability when storing the optical laminate with protective film of the present invention in a wound form, the substrate film preferably has a release agent layer. Excellent storage stability is contributed by forming the release agent layer from a resin composition comprising a release agent mainly composed of dimethylpolysiloxane and an antistatic agent.

[0031] The adhesive layer can be composed of (meth)acrylic adhesives, epoxy adhesives, urethane adhesives, silicone adhesives, etc.

[0032] Alternatively, the protective film can also be a self-adhesive resin film such as polypropylene or polyethylene resin. In this case, the protective film does not have an adhesive layer.

[0033] The thickness of the protective film can be, for example, 5–150 μm, preferably 10–100 μm, more preferably 20–75 μm, and even more preferably 25–70 μm (e.g., 35 μm or more and 60 μm or less, or even 40 μm or more and 55 μm or less). When the thickness of the protective film is less than 5 μm, the protection of the optical laminate becomes insufficient, and it is also detrimental in terms of operability and storage stability. A protective film thickness exceeding 150 μm is disadvantageous in terms of the thinning of the optical laminate with the protective film and the reworkability of the protective film, as described later.

[0034] Regarding the optical laminate with protective film of the present invention, when the tensile elastic modulus of the optical laminate in the direction parallel to the MD direction is set as E1 and the tensile elastic modulus of the protective film in the direction parallel to the MD direction is set as E2, their ratio E1 / E2 can satisfy E1 / E2 < 10, preferably less than 6, more preferably less than 2, and even more preferably less than 1. E1 / E2 can be, for example, 0.01 or more. By making E1 / E2 satisfy the above-mentioned numerical range, excellent storage stability can be obtained when the optical laminate with protective film of the present invention is stored in a wound form, which is therefore preferred.

[0035] Furthermore, regarding the optical laminate with protective film of the present invention, when the tensile elastic modulus of the optical laminate in the direction parallel to the TD direction is set to E3 and the tensile elastic modulus of the protective film in the direction parallel to the TD direction is set to E4, their ratio E3 / E4 can satisfy E3 / E4 < 10, preferably less than 6, more preferably less than 2, and even more preferably less than 1. E3 / E4 can be, for example, 0.01 or more. By simultaneously satisfying the above-mentioned numerical ranges for E3 / E4 and E1 / E2, further excellent storage stability can be obtained when the optical laminate with protective film of the present invention is stored in a wound form, which is therefore preferred.

[0036] The absolute value of the difference between the tensile modulus ratios E1 / E2 and E3 / E4 of the optical laminate with protective film of the present invention, |MD(E1 / E2)-(E3 / E4)|, is preferably less than 2, and more preferably less than 1. By ensuring that the absolute value of the aforementioned tensile modulus difference meets the above-mentioned numerical range, as described below, it becomes easier to peel the protective film from the optical laminate with protective film, thereby improving operability.

[0037] Regarding the optical laminate with a protective film of the present invention, when the rigidity of the optical laminate in the direction parallel to the MD direction is set as S1, and the rigidity of the protective film in the direction parallel to the MD direction is set as S2, the absolute value of their difference |S1-S2| is preferably 400 or less, more preferably 300 or less, more preferably 5 or more, and more preferably 20 or more. By making |S1-S2| satisfy the above-mentioned numerical range, as described below, it becomes easier to peel the protective film from the optical laminate with the protective film, thus improving operability, and is therefore preferred. It should be noted that the rigidity referred to here is the product of the tensile elastic modulus and the film thickness.

[0038] Furthermore, regarding the optical laminate with a protective film of the present invention, when the rigidity of the optical laminate in the direction parallel to the TD direction is set to S3 and the rigidity of the protective film in the direction parallel to the TD direction is set to S4, the absolute value of their difference |S3-S4| is preferably 400 or less, more preferably 300 or less, more preferably 5 or more, and more preferably 20 or more. By making |S3-S4| satisfy the above-mentioned numerical range, as described later, it becomes easier to peel the protective film from the optical laminate with the protective film, thus improving operability, which is preferred.

[0039] [First Optical Anisotropy Layer] In this invention, the first optical anisotropy layer can be, for example, a cured polymeric liquid crystal composition obtained by curing a stretched film or a polymeric liquid crystal compound in a state of vertical orientation relative to the film plane (hereinafter also referred to as a "vertically oriented liquid crystal cured film") layer.

[0040] Examples of stretched films include uniaxially stretched polycarbonate (PC) films, uniaxially stretched cellulose triacetate (TAC) films, and uniaxially stretched cyclic olefin polymer (COP) films. The optical properties of these stretched films, such as in-plane phase difference and thickness-direction phase difference, can be adjusted by controlling the composition of the resin constituting the stretched film, the stretching method, and the thickness of the stretched film.

[0041] The cured polymeric liquid crystal composition, obtained by curing a polymeric liquid crystal compound in a state perpendicular to the film plane ("vertically oriented liquid crystal cured film"), can be formed using nematic liquid crystal or discoid liquid crystal. The optical properties of the cured polymeric liquid crystal composition, such as the in-plane phase difference and the phase difference in the thickness direction, can be adjusted by controlling the type of polymeric liquid crystal compound, the orientation state of the cured polymeric liquid crystal compound, and the thickness of the cured layer.

[0042] The thickness of the first optical anisotropic layer is typically 0.1 μm to 3 μm, preferably 0.3 μm to 2 μm, and more preferably 0.5 μm to 1.5 μm. By ensuring the thickness of the first optical anisotropic layer meets the above-mentioned range, both lightweight design and optical performance of the image display device can be achieved. Furthermore, from the viewpoint of achieving such a thickness, the first optical anisotropic layer is preferably a cured product of a polymeric liquid crystal composition obtained by curing a polymeric liquid crystal compound in a state where it is oriented perpendicularly to the film plane.

[0043] Furthermore, the first optical anisotropic layer preferably satisfies the following equation (1).

[0044] nx≈ny<nz (1) In equation (1), nx represents the principal refractive index in the direction parallel to the film plane of the refractive index ellipsoid formed by the optical anisotropic layer. ny represents the principal refractive index in the direction parallel to the film plane and orthogonal to the direction of nx in the refractive index ellipsoid formed by the optical anisotropic layer. nz represents the principal refractive index in the direction perpendicular to the film plane in the refractive index ellipsoid formed by the optical anisotropic layer. Here, nx, ny, and nz each represent the principal refractive index relative to light with a wavelength of 550 nm. By making the first optical anisotropic layer satisfy the above equation (1), when the optical laminate of the present invention is used in an image display device as described later, the effects of preventing light leakage and color shift during visual recognition from an oblique direction when displaying black can be obtained.

[0045] Furthermore, the first optical anisotropic layer preferably satisfies the following equation (2).

[0046] 5nm≤R'40(550)≤30nm (2) [In equation (2), R'40 (550) represents the phase difference when the first optical anisotropic layer is tilted by 40 degrees at a wavelength of 550 nm.] R'40 (550) is more preferably 28 nm or less, and even more preferably 26 nm or less. By satisfying the above numerical range, when the optical laminate of the present invention is used in an image display device, it is possible to obtain the effect of further preventing light leakage and color shift when visually recognizing the black display from an oblique direction.

[0047] In the optical laminate of the present invention, the first optical anisotropic layer more preferably satisfies the following formula (3).

[0048] R'40 (450) / R'40 (550) ≤ 1.04 (3) In equation (3), R'40 (450) represents the phase difference value when the first optical anisotropic layer is tilted by 40 degrees at a wavelength of 450 nm, and R'40 (550) represents the phase difference value when the first optical anisotropic layer is tilted by 40 degrees at a wavelength of 550 nm. R'40 (450) / R'40 (550) is more preferably 1.02 or less, and even more preferably 1.00 or less. By satisfying the above numerical range, when the optical laminate of the present invention is used in an image display device, the effect of further preventing light leakage and color shift when visually recognizing the image from the tilt direction during black display can be obtained.

[0049] In this invention, regarding R'40 (550) of Equation (2), that is, the phase difference value when the first optical anisotropic layer is tilted by 40 degrees at a wavelength of 550 nm, as an example, it can be measured in the following manner. A sample with the first optical anisotropic layer formed on a substrate such as a glass substrate that has no phase difference is prepared by the method described later. Then, by using a phase difference measuring device (manufactured by Oji Measurement Equipment Co., Ltd., KOBRA-WPR), the fast axis is set as the tilt center and the sample is tilted by 40° and the measurement is performed, R'40 (550) can be obtained. R'40 (450) of Equation (3), that is, the phase difference value when the first optical anisotropic layer is tilted by 40 degrees at a wavelength of 450 nm, is also measured by the same method as R'40 (550).

[0050] In this invention, when the first optical anisotropy layer is a vertically oriented liquid crystal curing film, the polymeric liquid crystal compound contained in the polymeric liquid crystal composition forming the vertically oriented liquid crystal curing film means a liquid crystal compound having polymeric groups, and particularly preferably a polymeric liquid crystal compound having at least one free radical polymeric group.

[0051] A polymerizable group refers to a group that can participate in a polymerization reaction through active free radicals, acids, etc., generated by a polymerization initiator. Examples of polymerizable groups include vinyl, vinyloxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, acryloyloxy, methacryloyloxy, oxetylpropyl, and oxetylbutyl. Among these, free radical polymerizable groups are preferred, acryloyloxy, methacryloyloxy, vinyl, and vinyloxy are more preferred, and acryloyloxy and methacryloyloxy are even more preferred.

[0052] The liquid crystal properties exhibited by polymerizable liquid crystal compounds can be either thermotropic or lyotropic. From the perspective of enabling precise film thickness control, thermotropic liquid crystals are preferred.

[0053] Examples of polymeric liquid crystal compounds include polymeric liquid crystal compounds that typically exhibit positive wavelength dispersion and polymeric liquid crystal compounds that exhibit reverse wavelength dispersion. Either polymeric liquid crystal compound can be used alone, or two polymeric liquid crystal compounds can be mixed and used. From the viewpoint of preventing light leakage and color shift when visually recognizing the object from an oblique direction in black display, it is preferable to adjust the composition so that the first optical anisotropy layer satisfies the aforementioned formula (3).

[0054] As a polymeric liquid crystal compound exhibiting reverse wavelength dispersion, a compound having the characteristics described in (A) to (D) below is preferred.

[0055] (A) is a compound that can form a nematic or smectic phase.

[0056] (B) The polymeric liquid crystal compound has π electrons in the long axis direction (a).

[0057] (C) It has π electrons in the direction intersecting the major axis direction (a) [intersecting direction (b)].

[0058] (D) The total number of π electrons present in the long axis direction (a) is denoted as N(πa), and the total number of molecular weights present in the long axis direction is denoted as N(Aa). The π electron density in the long axis direction (a) of the polymeric liquid crystal compound is defined by the following formula (i): D(πa)=N(πa) / N(Aa) (i), and, The total number of π electrons present in the cross direction (b) is denoted as N(πb), and the total number of molecular weights present in the cross direction (b) is denoted as N(Ab). The π electron density in the cross direction (b) of the polymeric liquid crystal compound is defined by the following formula (ii): D(πb)=N(πb) / N(Ab)(ii) The relation of existence (iii): 0≤〔D(πa) / D(πb)〕<1 (iii) [That is, the π electron density in the cross direction (b) is greater than the π electron density in the major axis direction (a).]

[0059] Furthermore, as described above, polymeric liquid crystal compounds having π electrons along their long axis and in the direction intersecting it become, for example, T-shaped structures.

[0060] Among the features (A) to (D) above, the major axis direction (a) and the number of π electrons N are defined as follows.

[0061] • For the long axis direction (a), for example, in the case of a compound with a rod-like structure, it is the long axis direction of its rod shape.

[0062] • The number of π electrons N (πa) present in the long axis direction (a) does not include π electrons that disappear through polymerization.

[0063] • The number of π electrons N(πa) present in the major axis direction (a) is the sum of the π electrons on the major axis and their conjugate π electrons, for example, the number of π electrons present in the rings present in the major axis direction (a) and satisfying Hückel's rule.

[0064] • The number of π electrons N (πb) present in the cross direction (b) does not include π electrons that disappear through the polymerization reaction.

[0065] The polymerizable liquid crystal compound satisfying the above conditions has a mesocrystalline structure along its long axis. This mesocrystalline structure allows it to exhibit a liquid crystal phase (nematic phase, smectic phase).

[0066] By coating a polymeric liquid crystal compound satisfying (A) to (D) above onto a film (layer) to be formed as a liquid crystal curable film, and heating it above the phase transition temperature, a liquid crystal phase such as a nematic or smectic phase can be formed. The liquid crystal phase formed by aligning this polymeric liquid crystal compound is typically aligned such that the long axes of the polymeric liquid crystal compounds are parallel to each other, and this long axis direction is called the orientation direction of the liquid crystal phase. If such a polymeric liquid crystal compound is made into a film and polymerized in the liquid crystal phase state, a polymer film formed from a polymer polymerized in a state aligned along the long axis direction (a) can be formed. This polymer film absorbs ultraviolet light through π electrons in the long axis direction (a) and π electrons in the cross direction (b). Here, the wavelength of maximum absorption of ultraviolet light absorbed by π electrons in the cross direction (b) is denoted as λbmax. λbmax is typically 300 nm to 400 nm. The density of π electrons satisfies equation (iii) above. The density of π electrons in the cross direction (b) is greater than that in the major axis direction (a). Therefore, this polymer film has a higher absorption of linearly polarized ultraviolet light (wavelength λbmax) with a vibrational surface in the cross direction (b) than with the same light in the major axis direction (a). The ratio (absorbance of linearly polarized ultraviolet light in the cross direction (b) / absorbance in the major axis direction (a)) is, for example, greater than 1.0, preferably greater than 1.2, typically less than 30, and for example less than 10.

[0067] Polymer liquid crystal compounds exhibiting reverse wavelength dispersion can be exemplified by compounds represented by the following formula (X) (hereinafter also referred to as "polymer liquid crystal compound (X)").

[0068] [Chemical Formula 1] In formula (X), Ar represents a divalent group containing an aromatic group that may have substituents. The aromatic group referred to here is a group whose ring structure has [4n+2] π electrons according to Hückel's rule, such as an Ar group that may have two or more π electrons as exemplified later in (Ar-1) to (Ar-23) via a divalent linking group. Here, n represents an integer. In the case of a ring structure formed by including heteroatoms such as -N= and -S-, this also includes cases where the non-covalent electron pairs on these heteroatoms satisfy Hückel's rule and thus possess aromaticity. Preferably, the aromatic group contains at least one of nitrogen, oxygen, or sulfur atoms. The divalent group Ar may contain one or more aromatic groups. In the case of one aromatic group, the divalent group Ar may be a divalent aromatic group that may have substituents. When the divalent group Ar contains two or more aromatic groups, the two or more aromatic groups can be bonded to each other by single bonds, -CO-O-, -O- and other divalent bonding groups.

[0069] G 1 and G 2 Each of these groups independently represents a divalent aromatic group or a divalent alicyclic hydrocarbon group. Here, the hydrogen atom contained in the divalent aromatic group or divalent alicyclic hydrocarbon group may be replaced by a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group, or a nitro group, and the carbon atom constituting the divalent aromatic group or divalent alicyclic hydrocarbon group may be replaced by an oxygen atom, a sulfur atom, or a nitrogen atom.

[0070] L 1 L 2 B 1 and B 2 Each is an independent linking group that is either a single bond or divalent.

[0071] k and l each independently represent integers from 0 to 3, satisfying the relationship 1 ≤ k + l. Here, in the case of 2 ≤ k + l, B 1 With B 2 G 1 With G 2 They can be the same as each other, or they can be different.

[0072] E 1 and E 2 Each alkanediyl group independently represents an alkanediyl group with 1 to 17 carbon atoms, and more preferably an alkanediyl group with 4 to 12 carbon atoms. In addition, the hydrogen atoms contained in the alkanediyl group can be replaced by halogen atoms, and the -CH2- contained in the alkanediyl group can be replaced by -O-, -S-, -SiH2-, or -C(=O)-.

[0073] P 1 and P 2 Each of the above can be represented independently as a polymeric group or a hydrogen atom, with at least one being a polymeric group.

[0074] G 1 and G 2 Each of the following is preferably 1,4-phenylene diel, which can be substituted with at least one substituent selected from the group consisting of alkyl groups having 1 to 4 carbon atoms; or 1,4-cyclohexane diel, which can be substituted with at least one substituent selected from the group consisting of alkyl groups having 1 to 4 carbon atoms; more preferably methyl-substituted 1,4-phenylene diel, unsubstituted 1,4-phenylene diel, or unsubstituted 1,4-trans-cyclohexane diel; and particularly preferably unsubstituted 1,4-phenylene diel or unsubstituted 1,4-trans-cyclohexane diel.

[0075] In addition, it is preferable that there are multiple Gs. 1 and G 2 At least one of them is a divalent alicyclic hydrocarbon group, and more preferably it is with L 1 or L 2 bonded G 1 and G 2 At least one of them is a divalent alicyclic hydrocarbon group.

[0076] L 1 and L 2 Each is preferably a single bond, an alkylene group having 1 to 4 carbon atoms, and a -O-, -S-, or -R group. a1 OR a2 -、-R a3 COOR a4 -、-R a5 OCOR a6 -、R a7 OC = OOR a8 -、-N=N-、-CR c =CR d -、or -C≡C-. Here, R a1 ~R a8 Each independently represents a single bond, or an alkylene group having 1 to 4 carbon atoms, R c and R d L represents an alkyl group or hydrogen atom with 1 to 4 carbon atoms. 1 and L 2 Each independently is more preferably a single bond, -OR a2-1 -、-CH2-、-CH2CH2-、-COOR a4-1 -、or-OCOR a6-1 -. Here, R a2-1 R a4-1 R a6-1Each can independently represent any one of a single bond, -CH2-, or -CH2CH2-. L 1 and L 2 Each of these can be further preferred independently as a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, or -OCO-.

[0077] B 1 and B 2 Each is preferably a single bond, an alkylene group having 1 to 4 carbon atoms, and a -O-, -S-, or -R group. a9 OR a10 -、-R a11 COOR a12 -、-R a13 OCOR a14 - or -R a15 OC = OOR a16 -. Here, R a9 ~R a16 Each can independently represent a single bond or an alkylene group having 1 to 4 carbon atoms. B 1 and B 2 Each independently is more preferably a single bond, -OR a10-1 -、-CH2-、-CH2CH2-、-COOR a12 -1 -、or-OCOR a14-1 -. Here, R a10-1 R a12-1 R a14-1 Each can independently represent any one of a single bond, -CH2-, or -CH2CH2-. B 1 and B 2 Each of these can be further preferred independently as a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, -OCO-, or -OCOCH2CH2-.

[0078] For k and l, from the viewpoint of exhibiting inverse wavelength dispersion, the range of 2≤k+l≤6 is preferred, k+l=4 is preferred, and k=2 and l=2 is more preferred. When k=2 and l=2, a symmetrical structure is formed, which is therefore preferred.

[0079] As P 1 or P 2 Examples of polymerizable groups include epoxy, vinyl, vinyloxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, acryloyloxy, methacryloyloxy, oxetylpropyl, and oxetylbutyl. Acryloyloxy, methacryloyloxy, vinyl, and vinyloxy are preferred, and acryloyloxy and methacryloyloxy are more preferred.

[0080] Ar preferably has at least one selected from aromatic hydrocarbon rings that may have substituents, aromatic heterocycles that may have substituents, and electron-withdrawing groups. Examples of such aromatic hydrocarbon rings include benzene rings, naphthyl rings, and anthracene rings, with benzene rings and naphthyl rings being preferred. Examples of such aromatic heterocycles include furan rings, benzofuran rings, pyrrole rings, indole rings, thiophene rings, benzothiophene rings, pyridine rings, pyrazine rings, pyrimidine rings, triazole rings, triazine rings, pyrrolidine rings, imidazole rings, pyrazole rings, thiazole rings, benzothiazole rings, thienothiazole rings, oxazole rings, benzoxazole rings, and phenanthroline rings. Among these, a thiazole ring, a benzothiazole ring, or a benzofuran ring is preferred, and a benzothiazole group is even more preferred. Furthermore, if Ar contains a nitrogen atom, the nitrogen atom preferably has π electrons.

[0081] In formula (X), N represents the total number of π electrons contained in the divalent aromatic group, Ar. π Preferably, the value is 8 or more, more preferably 10 or more, even more preferably 14 or more, and particularly preferably 16 or more. Furthermore, it is preferably 30 or less, more preferably 26 or less, and even more preferably 24 or less.

[0082] Ar can be represented by the following aromatic groups, for example.

[0083] [Chemical Formula 2] In equations (Ar-1) to (Ar-23), the symbols... Z represents the connecting part. 0 Z 1 and Z 2 Each of these groups independently represents a hydrogen atom, a halogen atom, an alkyl group (1-12 carbon atoms), a cyano group, a nitro group, an alkylsulfinyl group (1-12 carbon atoms), an alkylsulfonyl group (1-12 carbon atoms), a carboxyl group, a fluoroalkyl group (1-12 carbon atoms), an alkoxy group (1-12 carbon atoms), an alkylthio group (1-12 carbon atoms), an N-alkylamino group (1-12 carbon atoms), an N,N-dialkylamino group (2-12 carbon atoms), an N-alkylaminosulfonyl group (1-12 carbon atoms), or an N,N-dialkylaminosulfonyl group (2-12 carbon atoms). Additionally, Z... 0 Z 1 and Z 2 It can contain polymeric groups.

[0084] Q 1 and Q 2 Each is represented independently - CR 2’ R 3’ -、-S-、-NH-、-NR 2’ -、-CO- or -O-, R 2’ and R 3’Each can be independently represented as an alkyl group having 1 to 4 hydrogen atoms or carbon atoms.

[0085] J 1 and J 2 Each can be used to represent a carbon atom or a nitrogen atom independently.

[0086] Y 1 Y 2 and Y 3 Each can be independently represented as a substituted aromatic hydrocarbon group or an aromatic heterocyclic group.

[0087] W 1 and W 2 Each can independently represent a hydrogen atom, cyano group, methyl group, or halogen atom, and m represents an integer from 0 to 6.

[0088] As Y 1 Y 2 and Y 3 The aromatic hydrocarbon group in the compound can include phenyl, naphthyl, anthraceneyl, phenanthryl, biphenyl, and other aromatic hydrocarbon groups with 6 to 20 carbon atoms, with phenyl and naphthyl being preferred, and phenyl being more preferred. As aromatic heterocyclic groups, can include furanyl, pyrroleyl, thiopheneyl, pyridyl, thiazolyl, benzothiazolyl, and other aromatic heterocyclic groups with 4 to 20 carbon atoms containing at least one heteroatom such as a nitrogen atom, oxygen atom, or sulfur atom, with furanyl, thiopheneyl, pyridyl, thiazolyl, and benzothiazolyl being preferred.

[0089] Y 1 Y 2 and Y 3 Each can be independently a substituted polycyclic aromatic hydrocarbon group or a polycyclic aromatic heterocyclic group. A polycyclic aromatic hydrocarbon group refers to a fused polycyclic aromatic hydrocarbon group or a group derived from an aromatic ring assembly. A polycyclic aromatic heterocyclic group refers to a fused polycyclic aromatic heterocyclic group or a group derived from an aromatic ring assembly.

[0090] Z 0 Z 1 and Z 2 Each of the following is preferably composed of a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, or an alkoxy group having 1 to 12 carbon atoms. 0 Further preferred are hydrogen atoms, alkyl groups having 1 to 12 carbon atoms, and cyano groups, Z. 1 and Z 2 Further preferred are hydrogen atoms, fluorine atoms, chlorine atoms, methyl groups, and cyano groups. Additionally, Z... 0 Z 1 and Z 2 It can contain polymeric groups.

[0091] Q 1 and Q 2Preferred types are -NH-, -S-, and -NR. 2’ -、-O-,R 2’ Hydrogen atoms are preferred. Among them, -S-, -O-, and -NH- are particularly preferred.

[0092] From the perspective of molecular stability, formulas (Ar-6) and (Ar-7) are preferred among formulas (Ar-1) to (Ar-23).

[0093] In formula (Ar-17) ~ (Ar-23), Y 1 It can bond with the nitrogen atom and Z 0 Together, they form an aromatic heterocyclic group. Examples of aromatic heterocycles that Ar can possess, as described above, include pyrrole rings, imidazole rings, pyrrololine rings, pyridine rings, pyrazine rings, pyrimidine rings, indole rings, quinoline rings, isoquinoline rings, purine rings, and pyrrolidine rings. This aromatic heterocyclic group can have substituents. Additionally, Y... 1 It can bond with the nitrogen atom and Z 0 Together, they form the aforementioned substituted polycyclic aromatic hydrocarbon groups or polycyclic aromatic heterocyclic groups. Examples include benzofuran rings, benzothiazole rings, and benzoxazole rings.

[0094] Furthermore, in this invention, as the polymeric liquid crystal compound for forming a vertically oriented liquid crystal cured film, for example, a compound containing a group represented by the following formula (Y) (hereinafter also referred to as "polymeric liquid crystal compound (Y)") can be used. Polymeric liquid crystal compounds generally tend to exhibit positive wavelength dispersion. Polymeric liquid crystal compounds can be used alone or in combination of two or more, and polymeric liquid crystal compound (X) can be used in combination with polymeric liquid crystal compound (Y).

[0095] P11-B11-E11-B12-A11-B13- (Y) In formula (Y), P11 represents a polymerizable group.

[0096] A11 represents a divalent alicyclic hydrocarbon group or a divalent aromatic hydrocarbon group. The hydrogen atom contained in the divalent alicyclic hydrocarbon group and the divalent aromatic hydrocarbon group may be replaced by a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a cyano group or a nitro group, and the hydrogen atom contained in the alkyl group having 1 to 6 carbon atoms and the alkoxy group having 1 to 6 carbon atoms may be replaced by a fluorine atom.

[0097] B11 represents -O-, -S-, -CO-O-, -O-CO-, -O-CO-O-, -CO-NR 16 -、-NR 16 -CO-, -CO-, -CS-, or a single bond. R16 It represents an alkyl group having 1 to 6 hydrogen atoms or carbon atoms.

[0098] B12 and B13 independently represent -C≡C-, -CH=CH-, -CH2-CH2-, -O-, -S-, -C(=O)-, -C(=O)-O-, -OC(=O)-O-, -OC(=O)-O-, -CH=N-, -N=CH-, -N=N-, -C(=O)-NR 16 -、-NR 16 -C(=O)-, -OCH2-, -OCF2-, -CH2O-, -CF2O-, -CH=CH-C(=O)-O-, -OC(=O)-CH=CH- or single bond.

[0099] E11 represents an alkane dierium with 1 to 12 carbon atoms, where the hydrogen atom in the dierium can be replaced by an alkoxy group with 1 to 5 carbon atoms, and the hydrogen atom in the alkoxy group can be replaced by a halogen atom. Furthermore, the -CH2- group constituting the dierium can be replaced by -O- or -CO-. The number of carbon atoms in the aromatic hydrocarbon group and alicyclic hydrocarbon group of A11 is preferably in the range of 3 to 18, more preferably in the range of 5 to 12, and particularly preferably 5 or 6. As A11, cyclohexane-1,4-diyl or 1,4-phenylene are preferred.

[0100] As E11, a linear alkane diester with 1 to 12 carbon atoms is preferred. The -CH2- constituting this alkane diester can be replaced with -O-.

[0101] Specifically, examples include straight-chain alkane dimethyl groups with 1 to 12 carbon atoms, such as methylene, ethylene, propane-1,3-diyl, butane-1,4-diyl, pentane-1,5-diyl, hexane-1,6-diyl, heptane-1,7-diyl, octane-1,8-diyl, nonane-1,9-diyl, decane-1,10-diyl, undecane-1,11-diyl, and dodecane-1,12-diyl; and -CH2-CH2-O-CH2-CH2-, -CH2-CH2-O-CH2-CH2-O-CH2-CH2-, and -CH2-CH2-O-CH2-CH2-O-CH2-CH2-.

[0102] As B11, -O-, -S-, -CO-O-, and -O-CO- are preferred, with -CO-O- being more preferred.

[0103] B12 and B13 are each preferably -O-, -S-, -C(=O)-, -C(=O)-O-, -OC(=O)-O-, and -OC(=O)-O-, with -O- or -OC(=O)-O- being more preferred.

[0104] As for the polymerizable group represented by P11, considering its high polymerization reactivity, especially photopolymerization reactivity, it is preferred to be a free radical polymerizable group or a cationic polymerizable group. Considering the ease of operation and the ease of manufacturing the liquid crystal compound itself, the polymerizable group is preferably a group represented by the following formulas (P-11) to (P-15).

[0105] [Chemical Formula 3] In equations (P-11) to (P-15), R 17 ~R 21 Each can independently represent an alkyl group or a hydrogen atom having 1 to 6 carbon atoms. As specific examples of the groups represented by formulas (P-11) to (P-15), the groups represented by formulas (P-16) to (P-20) can be cited below.

[0106] [Chemical Formula 4] P11 is preferably a group represented by formula (P-14) to formula (P-20), more preferably vinyl, p-stilbene, epoxy or oxocyclobutyl.

[0107] The group represented by P11-B11- is further preferably acryloyloxy or methacryloyloxy.

[0108] Examples of polymerizable liquid crystal compounds (Y) include compounds represented by formulas (I), (II), (III), (IV), (V), or (VI).

[0109] P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-A14-B16-E12-B17-P12 (I) P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-A14-F11 (II) P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-E12-B17-P12 (III) P11-B11-E11-B12-A11-B13-A12-B14-A13-F11 (IV) P11-B11-E11-B12-A11-B13-A12-B14-E12-B17-P12 (V) P11-B11-E11-B12-A11-B13-A12-F11 (VI) (In the formula, A12 to A14 are each independently the same as A11, B14 to B16 are each independently the same as B12, B17 is the same as B11, E12 is the same as E11, and P12 is the same as P11.

[0110] F11 represents a hydrogen atom, an alkyl group with 1 to 13 carbon atoms, an alkoxy group with 1 to 13 carbon atoms, a cyano group, a nitro group, a trifluoromethyl group, a dimethylamino group, a hydroxyl group, a hydroxymethyl group, a formyl group, a sulfonyl group (-SO3H), a carboxyl group, an alkoxy carbonyl group with 1 to 10 carbon atoms, or a halogen atom. The -CH2- group constituting the alkyl or alkoxy group can be replaced with -O-. Specific examples of polymerizable liquid crystal compounds (Y) include compounds containing polymerizable groups described in "3.8.6 Network (fully cross-linked type)" and "6.5.1 Liquid Crystal Materials b. Polymerizable Nematic Liquid Crystal Materials" of the Liquid Crystal Compendium (edited by the Liquid Crystal Compendium Editorial Committee, published by Maruzen Co., Ltd. on October 30, 2012), as well as polymerizable liquid crystals described in Japanese Patent Application Publication Nos. 2010-31223, 2010-270108, 2011-6360, and 2011-207765.

[0111] Specific examples of polymerizable liquid crystal compounds (Y) include those represented by formulas (I-1) to (I-10) below. It should be noted that in the following formulas, k1 and k2 each independently represent integers from 2 to 12. These polymerizable liquid crystal compounds (Y) are preferred from the perspective of ease of synthesis or ease of acquisition.

[0112] [Chemical Formula 5] In this invention, the vertically oriented liquid crystal cured film preferably has at least one maximum absorption wavelength between 300 and 400 nm, and the polymeric liquid crystal composition forming the vertically oriented liquid crystal cured film preferably contains at least one polymeric liquid crystal compound having a maximum absorption wavelength between 300 and 400 nm. When the polymeric liquid crystal composition contains a photopolymerization initiator, polymerization and gelation of the polymeric liquid crystal compound may occur during long-term storage. However, if the maximum absorption wavelength of the polymeric liquid crystal compound is 300-400 nm, even when exposed to ultraviolet light during storage, the generation of reactive species from the photopolymerization initiator and the polymerization and gelation of the polymeric liquid crystal compound caused by these reactive species can be effectively suppressed. Therefore, this is advantageous in terms of the long-term stability of the polymeric liquid crystal composition, and can improve the orientation and uniformity of the resulting liquid crystal cured film. It should be noted that the maximum absorption wavelength of the polymeric liquid crystal compound can be measured using a UV-Vis spectrophotometer in a solvent. This solvent is a solvent capable of dissolving the polymeric liquid crystal compound, such as chloroform.

[0113] Regarding the content of the polymeric liquid crystal compound in the polymeric liquid crystal composition for forming the vertically oriented liquid crystal cured film, it is, for example, 70 to 99.5 parts by mass, preferably 80 to 99 parts by mass, more preferably 85 to 98 parts by mass, and even more preferably 90 to 95 parts by mass, relative to 100 parts by mass of the solid component of the polymeric liquid crystal composition. When the content of the polymeric liquid crystal compound is within the above range, it is advantageous from the viewpoint of the orientation of the obtained liquid crystal cured film. It should be noted that, in this invention, the so-called solid component of the polymeric liquid crystal composition refers to all components after removing volatile components such as organic solvents from the polymeric liquid crystal composition.

[0114] In this invention, the polymerizable liquid crystal composition preferably comprises at least one polymerizable liquid crystal compound and a non-liquid crystal compound having at least one reactive group selected from acryloyloxy and methacryloxy (hereinafter sometimes referred to as a non-liquid crystal compound containing a reactive group). Preferably, it comprises 3 to 18 parts by mass of the non-liquid crystal compound containing a reactive group relative to 100 parts by mass of all polymerizable liquid crystal compounds. By including the non-liquid crystal compound containing a reactive group in the polymerizable liquid crystal composition, in addition to promoting vertical alignment, it is possible to suppress the change in phase difference value after the heat resistance test of the obtained liquid crystal cured film.

[0115] Examples of non-liquid crystal compounds containing reactive groups include monofunctional (meth)acrylates and polyfunctional (meth)acrylates. Monofunctional means having one reactive group, and polyfunctional means having multiple reactive groups. In this invention, the non-liquid crystal compound containing reactive groups constituting the optical anisotropic film is preferably selected from at least one of monofunctional (meth)acrylates and polyfunctional (meth)acrylates, more preferably from at least one of monofunctional and polyfunctional acrylates. From the viewpoint that the polymerization reaction between the polymerizable liquid crystal compound and the non-liquid crystal compound containing reactive groups can be easily and continuously carried out, polyfunctional acrylates are further preferred. One type of non-liquid crystal compound containing reactive groups can be used alone, or two or more can be used in combination. It should be noted that in this specification, (meth)acrylate refers to acrylate or methacrylate, and the same applies to (meth)acryloyloxy, etc. Furthermore, since the monofunctional (meth)acrylates and polyfunctional (meth)acrylates are non-liquid crystals, it is preferable that they do not have a mesocrystalline structure. Furthermore, in the coating of the optical anisotropic film forming composition, urethane structure, amino structure, epoxy structure, ethylene glycol structure and polyester structure may be included intramolecularly within a range that does not disturb the liquid crystal phase of the polymerizable liquid crystal compound contained therein.

[0116] Monofunctional (meth)acrylates are compounds that have one (meth)acryloyloxy group in the molecule [i.e., acryloyloxy (CH2=CHCOO-) or methacryloyloxy (CH2=C(CH3)COO-)].

[0117] Examples of monofunctional (meth)acrylates having one (meth)acryloyloxy group include alkyl (meth)acrylates with 4 to 16 carbon atoms, β-carboxyalkyl (meth)acrylates with 2 to 14 carbon atoms, alkylated phenyl (meth)acrylates with 2 to 14 carbon atoms, methoxy polyethylene glycol (meth)acrylates, phenoxy polyethylene glycol (meth)acrylates, and isobornyl (meth)acrylate.

[0118] Polyfunctional (meth)acrylates refer to compounds having two or more (meth)acryloyloxy groups within the molecule. In this invention, the polyfunctional (meth)acrylates used as non-liquid crystal compounds containing reactive groups preferably have 2 to 8 (meth)acryloyloxy groups within the molecule.

[0119] Examples of difunctional (meth)acrylates having two (meth)acryloyloxy groups include 1,3-butanediol di(meth)acrylate; 1,3-butanediol (meth)acrylate; 1,6-hexanediol di(meth)acrylate; ethylene glycol di(meth)acrylate; diethylene glycol di(meth)acrylate; neopentyl glycol di(meth)acrylate; triethylene glycol di(meth)acrylate; tetraethylene glycol di(meth)acrylate; polyethylene glycol diacrylate; bis(acryloyloxyethyl) ether of bisphenol A; ethoxylated bisphenol A di(meth)acrylate; propoxylated neopentyl glycol di(meth)acrylate; ethoxylated neopentyl glycol di(meth)acrylate; and 3-methylpentyl glycol di(meth)acrylate, etc.

[0120] Examples of polyfunctional (meth)acrylates having 3 to 6 (meth)acryloyloxy groups include: Trimethylolpropane tri(meth)acrylate; Pentaerythritol tri(meth)acrylate; Tris(2-hydroxyethyl)isocyanurate tri(meth)acrylate; Ethoxylated trimethylolpropane tri(meth)acrylate; Propoxylated trimethylolpropane tri(meth)acrylate; Pentaerythritol tetra(meth)acrylate; Dipentaerythritol penta(meth)acrylate; Dipentaerythritol hexa(meth)acrylate; Tripentaerythritol tetra(meth)acrylate; Tripentaerythritol penta(meth)acrylate; Tripentaerythritol hexa(meth)acrylate; Tripentaerythritol hepta(meth)acrylate; Tripentaerythritol octa(meth)acrylate; The reaction products of pentaerythritol tri(meth)acrylate and acid anhydride; the reaction products of dipentaerythritol penta(meth)acrylate and acid anhydride; the reaction products of tripentaerythritol hepta(meth)acrylate and acid anhydride; Caprolactone-modified trimethylolpropane tri(meth)acrylate; caprolactone-modified pentaerythritol tri(meth)acrylate; caprolactone-modified tri(2-hydroxyethyl)isocyanurate tri(meth)acrylate; caprolactone-modified pentaerythritol tetra(meth)acrylate; caprolactone-modified dipentaerythritol penta(meth)acrylate; caprolactone-modified dipentaerythritol hexa(meth)acrylate; caprolactone-modified tripentaerythritol tetra(meth)acrylate; caprolactone-modified tripentaerythritol tetra(meth)acrylate; Pentylenetetroxide pentamethacrylate; caprolactone-modified pentapentaerythritol hexamethacrylate; caprolactone-modified pentapentaerythritol heptamethacrylate; caprolactone-modified pentapentaerythritol octamethacrylate; reactants of caprolactone-modified pentapentaerythritol trimethacrylate and acid anhydrides; reactants of caprolactone-modified dipentaerythritol pentamethacrylate and acid anhydrides; and reactants of caprolactone-modified pentapentaerythritol heptamethacrylate and acid anhydrides, etc. It should be noted that caprolactone modification refers to the introduction of an open-ring form or open-ring polymer of caprolactone between the alcohol-derived portion and the methacryloyloxy group of the (meth)acrylate compound.

[0121] Examples of polyfunctional (meth)acrylates having seven or more (meth)acryloyloxy groups include: pentaerythritol hepta(meth)acrylate; pentaerythritol octa(meth)acrylate; reactants of pentaerythritol hepta(meth)acrylate with acid anhydrides; caprolactone-modified pentaerythritol hepta(meth)acrylate; caprolactone-modified pentaerythritol octa(meth)acrylate; and reactants of caprolactone-modified pentaerythritol hepta(meth)acrylate with acid anhydrides.

[0122] Commercially available multifunctional (meth)acrylates can also be used as non-liquid crystal compounds containing reactive groups. Examples of such commercially available products include, for instance, A-DOD-N, A-HD-N, A-NOD-N, APG-100, APG-200, APG-400, A-GLY-9E, A-GLY-20E, A-TMM-3, A-TMPT, AD-TMP, ATM-35E, A-TMMT, A-9550, A-DPH, HD-N, NOD-N, NPG, TMPT (all manufactured by Shin-Nakamura Chemical Co., Ltd.), ARONIX M-220, ARONIX M-325, ARONIX M-240, ARONIX M-270, ARONIX M-309, ARONIX M-310, ARONIX M-321, ARONIX M-350, ARONIX M-360, ARONIX M-305, ARONIX M-306, and ARONIX M-306. M-450, ARONIX M-451, ARONIX M-408, ARONIX M-400, ARONIX M-402, ARONIX M-403, ARONIX M-404, ARONIX M-405, ARONIX M-406 (all manufactured by Toa Gosei Co., Ltd.), EBECRYL11, EBECRYL145, EBECRYL150, EBECRYL40, EBECRYL140, EBECRYL180, DPGDA, HDDA, TPGDA, HPNDA, PETIA, PETRA, TMPTA, TMPEOTA, DPHA, EBECRYL series (all manufactured by Daicel Cytec Co., Ltd.), etc.

[0123] Preferred polyfunctional (meth)acrylates include compounds represented by the following formulas (B-1) to (B-14).

[0124] [Chemical Formula 6] The non-liquid crystal compound containing reactive groups preferably has 2 to 12 reactive groups within its molecule, more preferably 2 to 12 polymerizable groups within its molecule, and even more preferably a polyfunctional (meth)acrylate having 2 to 12 polymerizable groups within its molecule. From the viewpoint of more easily improving film strength, the non-liquid crystal compound containing reactive groups preferably has 3 or more reactive groups (number of polymerizable groups) within one molecule, more preferably 4 or more, and even more preferably 5 or more. The non-liquid crystal compound containing reactive groups preferably has 10 or fewer polymerizable groups within one molecule, more preferably 9 or fewer, and even more preferably 8 or fewer.

[0125] In this invention, the reactive groups (polymerizable groups) of the non-liquid crystal compound containing reactive groups are preferably the same as those of the polymerizable liquid crystal compound. It should be noted that when at least one compound selected from the polymerizable liquid crystal compound and the non-liquid crystal compound containing reactive groups has multiple reactive groups, it is preferable that at least one polymerizable group of the polymerizable liquid crystal compound is the same as at least one reactive group of the non-liquid crystal compound containing reactive groups. For example, when the non-liquid crystal compound containing reactive groups is a monofunctional (meth)acrylate, it is preferable that the polymerizable liquid crystal compound also has a (meth)acryloyloxy group. When the non-liquid crystal compound containing reactive groups is a polyfunctional (meth)acrylate, it is preferable that the polymerizable liquid crystal compound also has a (meth)acryloyloxy group.

[0126] Relative to 100 parts by mass of all polymerizable liquid crystal compound in the composition, the content of the non-liquid crystal compound containing reactive groups in the polymerizable liquid crystal composition is preferably 3 parts by mass or more and 18 parts by mass or less. The non-liquid crystal compound containing reactive groups is less likely to disrupt the orientation of the polymerizable liquid crystal compound, and while exhibiting high vertical orientation, it easily suppresses changes in phase difference after heat resistance testing. From the viewpoint of balancing appropriate phase difference suppression capability with the orientation order of the polymerizable liquid crystal compound, the content of the non-liquid crystal compound containing reactive groups is more preferably 5 parts by mass or more, and even more preferably 15 parts by mass or less, relative to 100 parts by mass of all polymerizable liquid crystal compound.

[0127] The weight-average molecular weight of the non-liquid crystal compound containing reactive groups is preferably 1200 or less, more preferably 1000 or less, and even more preferably 100 or more, more preferably 200 or more. If the weight-average molecular weight of the non-liquid crystal compound containing reactive groups is within the aforementioned range, it is easier to suppress changes in phase difference after the heat resistance test while maintaining high vertical orientation. The weight-average molecular weight of the non-liquid crystal compound containing reactive groups can be determined, for example, by gel permeation chromatography (GPC).

[0128] Regarding the content of the non-liquid crystal compound containing reactive groups in the first optical anisotropy layer, it is preferably 3 to 18 parts by mass relative to 100 parts by mass of the polymeric liquid crystal compound constituting the polymeric liquid crystal composition. If the content of the non-liquid crystal compound containing reactive groups is within the aforementioned range, the non-liquid crystal compound containing reactive groups is less likely to disrupt the orientation of the polymeric liquid crystal compound, and while possessing high vertical orientation, it is easier to suppress changes in phase difference after the heat resistance test. From the viewpoint of balancing appropriate phase difference suppression capability with the orientation order of the polymeric liquid crystal compound, the content of the non-liquid crystal compound containing reactive groups is more preferably 5 parts by mass or more, and even more preferably 15 parts by mass or less, relative to 100 parts by mass of the polymeric liquid crystal compound constituting the first optical anisotropy film.

[0129] The polymeric liquid crystal composition used in the formation of vertically oriented liquid crystal cured films may also contain additives such as solvents, polymerization initiators, leveling agents, antioxidants, and photosensitizers, in addition to polymeric liquid crystal compounds and vertical orientation promoters. Only one of these components may be used, or two or more may be used in combination.

[0130] The polymeric liquid crystal composition used in the formation of vertically aligned liquid crystal cured films is typically coated onto a substrate, vertically aligned film, etc., in a solvent-dissolved state, and therefore preferably contains a solvent. As a solvent, a solvent capable of dissolving the polymeric liquid crystal compound is preferred; furthermore, a solvent that is inactive for the polymerization reaction of the polymeric liquid crystal compound is preferred. Examples of solvents include, for instance, water, methanol, ethanol, ethylene glycol, isopropanol, propylene glycol, ethylene glycol methyl ether, ethylene glycol butyl ether, 1-methoxy-2-propanol, 2-butoxyethanol, and propylene glycol monomethyl ether; ester solvents such as ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone, propylene glycol methyl ether acetate, and ethyl lactate; ketone solvents such as acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, 2-heptanone, and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as pentane, hexane, and heptane; alicyclic hydrocarbon solvents such as ethylcyclohexane; aromatic hydrocarbon solvents such as toluene and xylene; nitrile solvents such as acetonitrile; ether solvents such as tetrahydrofuran and dimethoxyethane; chlorine-containing solvents such as chloroform and chlorobenzene; and amide solvents such as dimethylacetamide, dimethylformamide, N-methyl-2-pyrrolidone (NMP), and 1,3-dimethyl-2-imidazolinone. These solvents can be used alone or in combination of two or more. Among them, alcohol solvents, ester solvents, ketone solvents, chlorinated solvents, amide solvents, and aromatic hydrocarbon solvents are preferred.

[0131] The solvent content in the polymeric liquid crystal composition is preferably 50 to 98 parts by weight, more preferably 70 to 95 parts by weight, relative to 100 parts by weight of the polymeric liquid crystal composition. Therefore, the solid component preferably accounts for 2 to 50 parts by weight of the polymeric liquid crystal composition. If the solid component is 50 parts by weight or less, the viscosity of the polymeric liquid crystal composition becomes lower, and thus the film thickness becomes approximately uniform, with a tendency to avoid unevenness. The above-mentioned solid component can be appropriately determined considering the thickness of the liquid crystal cured film to be manufactured.

[0132] Polymerization initiators are compounds that generate reactive species through the contribution of heat or light, and can initiate polymerization reactions of polymerizable liquid crystal compounds, etc. Examples of reactive species include free radicals, cationic or anionic species. From the viewpoint of easy reaction control, photopolymerization initiators that generate free radicals through light irradiation are preferred.

[0133] Examples of photopolymerization initiators include benzoin compounds, benzophenone compounds, benzoyl ketal compounds, α-hydroxy ketone compounds, α-amino ketone compounds, oxime compounds, triazine compounds, iodonium salts, and matte salts. Specifically, examples include Irgacure (イルガキュア, registered trademark) 907, Irgacure 184, Irgacure 651, Irgacure 819, Irgacure 250, Irgacure 369, Irgacure 379, Irgacure 127, Irgacure 2959, Irgacure 754, Irgacure 379EG (all manufactured by BASF Japan Co., Ltd.), SEIKUOL BZ, SEIKUOL Z, SEIKUOL BEE (all manufactured by Seiko Chemical Co., Ltd.), kayacure (カヤキュアー) BP100 (manufactured by Nippon Kayaku Co., Ltd.), kayacure UVI-6992 (manufactured by DOW Corporation), and ADEKA OPTOMER. SP-152, ADEKA OPTOMER SP-170, ADEKA OPTOMER N-1717, ADEKA OPTOMER N-1919, ADEKA ARKLS NCI-831, ADEKA ARKLSNCI-930 (the above are made by ADEKA Co., Ltd.), TAZ-A, TAZ-PP (the above are made by Japan Siber Hegner Co., Ltd.) and TAZ-104 (the above are made by Sanwa Chemical Co., Ltd.).

[0134] For photopolymerization initiators, in order to make full use of the energy emitted by the self-light source and achieve excellent productivity, the maximum absorption wavelength is preferably 300nm to 400nm, more preferably 300nm to 380nm, wherein α-acetophenone-based polymerization initiators and oxime-based photopolymerization initiators are preferred.

[0135] Examples of α-acetophenone compounds include 2-methyl-2-morpholino-1-(4-methylthiophenyl)-1-propanone, 2-dimethylamino-1-(4-morpholinophenyl)-2-benzyl-1-butanone, and 2-dimethylamino-1-(4-morpholinophenyl)-2-(4-methylphenylmethyl)-1-butanone, with 2-methyl-2-morpholino-1-(4-methylthiophenyl)-1-propanone and 2-dimethylamino-1-(4-morpholinophenyl)-2-benzyl-1-butanone being more preferred. Commercially available α-acetophenone compounds include Irgacure 369, 379EG, 907 (all manufactured by BASF Japan Co., Ltd.) and SEIKUOL BEE (manufactured by Seiko Chemical Co., Ltd.).

[0136] Oxime-based photopolymerization initiators generate free radicals such as phenyl radicals and methyl radicals upon irradiation. These free radicals facilitate the polymerization of polymerizable liquid crystal compounds. Oxime-based photopolymerization initiators capable of generating methyl radicals are preferred from the perspective of high initiation efficiency of the polymerization reaction. Furthermore, from the viewpoint of making the polymerization reaction more efficient, photopolymerization initiators capable of efficiently utilizing ultraviolet light with wavelengths of 350 nm or higher are preferred. As photopolymerization initiators capable of efficiently utilizing ultraviolet light with wavelengths of 350 nm or higher, triazine compounds or carbazole compounds containing an oxime structure are preferred; from the viewpoint of sensitivity, carbazole compounds containing an oxime ester structure are more preferred. Examples of carbazole compounds containing an oxime ester structure include 1-[4-(phenylthio)]-1,2-octanedione 2-(O-benzoyl oxime) and 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-acetone 1-(O-acetyl oxime). Commercially available oxime ester-based photopolymerization initiators include Irgacure OXE-01, Irgacure OXE-02, Irgacure OXE-03 (all manufactured by BASF Japan Co., Ltd.), ADEKA OPTOMER N-1919, and ADEKA ARKLS NCI-831 (all manufactured by ADEKA Co., Ltd.).

[0137] The content of the photopolymerization initiator is typically 0.1 to 30 parts by mass relative to 100 parts by mass of the polymerizable liquid crystal compound, preferably 1 to 20 parts by mass, and more preferably 1 to 15 parts by mass. Within the above range, the reaction of the polymerizable groups proceeds sufficiently, and the orientation of the polymerizable liquid crystal compound is less likely to be disordered.

[0138] Leveling agents are additives that adjust the flowability of polymeric liquid crystal compositions and make the coating film obtained by coating the composition flatter. Examples of leveling agents include silicone-based, polyacrylate-based, and perfluoroalkyl-based agents.Commercially available products can be used as leveling agents. Specifically, examples include DC3PA, SH7PA, DC11PA, SH28PA, SH29PA, SH30PA, ST80PA, ST86PA, SH8400, SH8700, FZ2123 (all manufactured by Dow Corning Toray Co., Ltd.), KP321, KP323, KP324, KP326, KP340, KP341, X22-161A, KF6001 (all manufactured by Shin-Etsu Chemical Industry Co., Ltd.), TSF400, TSF401, TSF410, TSF4300, TSF4440, TSF4445, TSF-4446, TSF4452, and TSF4460 (all manufactured by Momentive Performance Materials Japan). Fluorinert (registered trademark) FC-72, FC-40, FC-43, FC-3283 (all manufactured by Sumitomo 3M Corporation), MEGAFACE (registered trademark) R-08, R-30, R-90, F-410, F-411, F-443, F-445, F-470, F-477, F-479, F-482, F-483, F-556 (all manufactured by DIC Corporation), EFTOP (trade name) EF301, EFTOP EF303, EFTOP EF351, EFTOP EF352 (all of the above are manufactured by Mitsubishi Materials Electronic Chemicals Co., Ltd.), Surflon (registered trademark) S-381, Surflon S-382, Surflon S-383, Surflon S-393, Surflon SC-101, Surflon SC-105, KH-40, SA-100 (all of the above are manufactured by AGC Seimi Chemical Co., Ltd.), trade name E1830, same as E5844 (manufactured by Daikin Fine Chemical Kenkyusho, KK), BM-1000, BM-1100, BYK-352, BYK-353 and BYK-361N (all trade name: BYK-Chemie Company), etc.Leveling agents can be used alone or in combination of two or more.

[0139] The leveling agent content is preferably 0.01 to 5 parts by mass relative to 100 parts by mass of the polymerizable liquid crystal compound, and more preferably 0.05 to 3 parts by mass. If the leveling agent content is within the above range, it tends to facilitate the orientation of the polymerizable liquid crystal compound and result in a smoother liquid crystal cured film, which is therefore preferred.

[0140] By incorporating an antioxidant, the polymerization reaction of the polymerizable liquid crystal compound can be controlled. The antioxidant can be a primary antioxidant selected from phenolic, amine, quinone, and nitroso antioxidants, or a secondary antioxidant selected from phosphorus and sulfur antioxidants. To polymerize the polymerizable liquid crystal compound without disrupting its orientation, the antioxidant content is typically 0.01 to 10 parts by weight, preferably 0.1 to 5 parts by weight, and more preferably 0.1 to 3 parts by weight, relative to 100 parts by weight of the polymerizable liquid crystal compound. The antioxidant can be used alone or in combination of two or more.

[0141] Furthermore, by using a photosensitizer, the sensitivity of the photopolymerization initiator can be increased. Examples of photosensitizers include: xanthones such as xanthones and thioxanthones; anthracene derivatives with substituents such as anthracene and alkyl ethers; thiophenazines; and rubrene. The photosensitizer can be used alone or in combination of two or more. The content of the photosensitizer is typically 0.01 to 10 parts by weight relative to 100 parts by weight of the polymerizable liquid crystal compound, preferably 0.05 to 5 parts by weight, and more preferably 0.1 to 3 parts by weight.

[0142] The polymeric liquid crystal composition used in the formation of vertically oriented liquid crystal cured films can be obtained by stirring a polymeric liquid crystal compound, a solvent, a photopolymerization initiator, and other components other than the polymeric liquid crystal compound at a specified temperature.

[0143] [Second optical anisotropy layer] In this invention, the second optical anisotropy layer, in addition to the stretching film and vertically oriented liquid crystal curing film exemplified in the first optical anisotropy layer, can be, for example, a substrate or a cured layer of a polymeric liquid crystal composition obtained by curing a substrate or a polymeric liquid crystal compound in a state of horizontal orientation relative to the film plane.

[0144] Similar to the films exemplified in the first optical anisotropic layer, examples of uniaxially stretched polycarbonate (PC) films, uniaxially stretched cellulose triacetate (TAC) films, and uniaxially stretched cyclic olefin polymer (COP) films can be cited as examples of stretched films. The optical properties of these stretched films, such as the in-plane phase difference value and the phase difference value in the thickness direction, can be adjusted by controlling the composition of the resin constituting the stretched film, the stretching method, and the thickness of the stretched film.

[0145] Examples of substrates include glass substrates and film substrates, but from a processability point of view, resin film substrates are preferred. Examples of resins constituting the film substrate include polyolefins such as polyethylene, polypropylene, and norbornene polymers; cyclic olefin resins; polyvinyl alcohol; polyethylene terephthalate; polymethacrylate; polyacrylate; cellulose esters such as cellulose triacetate, cellulose diacetate, and cellulose acetate propionate; polyethylene naphthalate; polycarbonate; polysulfone; polyethersulfone; polyetherketone; polyphenylene sulfide; and polyphenylene ether. Such resins can be used to form films using known methods such as solvent casting and melt extrusion to create the substrate. The substrate surface can have a protective layer formed from acrylic resin, methacrylic resin, epoxy resin, oxetane resin, urethane resin, melamine resin, etc., and can also undergo surface treatments such as silicone treatment for release, corona treatment, and plasma treatment.

[0146] Commercially available substrates can also be used for the second optical anisotropy layer. Examples of commercially available cellulose ester substrates include those manufactured by Fuji Photo Film Co., Ltd., such as Fujitack Film; and those manufactured by KONICA MINOLTA Opto Co., Ltd., such as “KC8UX2M”, “KC8UY”, and “KC4UY”. Examples of commercially available cyclic olefin resins include, for instance, cyclic olefin resins manufactured by Ticona (Germany) such as "Topas" (registered trademark); cyclic olefin resins manufactured by JSR Corporation such as "ARTON" (registered trademark); cyclic olefin resins manufactured by Zeon Corporation of Japan such as "ZEONOR" (registered trademark) and "ZEONEX" (registered trademark); cyclic olefin resins manufactured by Mitsui Chemicals Co., Ltd. such as "Apel" (registered trademark); and cyclic olefin resin base materials manufactured by Sekisui Chemicals Co., Ltd. such as "Escena" (registered trademark) and "SCA40" (registered trademark).

[0147] From the perspective of thinning of the laminate and the operability of the substrate, the thickness of the substrate is usually 5 to 300 μm, preferably 10 to 150 μm.

[0148] The second optical anisotropy layer can be a cured polymeric liquid crystal composition obtained by curing a polymeric liquid crystal compound in a horizontally oriented state relative to the film plane (hereinafter also referred to as a "horizontally oriented liquid crystal cured film"), or a liquid crystal cured film obtained by curing a polymeric liquid crystal compound having at least one free radical polymeric group in a horizontally oriented state relative to the in-plane direction of the cured film. By making the second optical anisotropy layer into a horizontally oriented liquid crystal cured film, it is possible to form it with a thinner thickness, thus enabling the lightweighting of the image display device.

[0149] The polymeric liquid crystal compound constituting the horizontally aligned liquid crystal cured film is not particularly limited; for example, polymeric liquid crystal compounds conventionally known in the field of retardation films can be used. Specifically, polymeric liquid crystal compound (X) or polymeric liquid crystal compound (Y) can be used, wherein, preferably, at least one polymeric liquid crystal compound exhibiting so-called reverse wavelength dispersion can be included, for example, polymeric liquid crystal compound (X) can be suitably used. In the polymeric liquid crystal composition for forming the horizontally aligned liquid crystal cured film, two or more polymeric liquid crystal compounds can be used alone or in combination, and polymeric liquid crystal compound (X) and polymeric liquid crystal compound (Y) can also be used in combination.

[0150] The content of the polymeric liquid crystal compound in the polymeric liquid crystal composition used to form the horizontally oriented liquid crystal cured film is, for example, 70 to 99.5 parts by mass, preferably 80 to 99 parts by mass, more preferably 85 to 98 parts by mass, and even more preferably 90 to 95 parts by mass, relative to 100 parts by mass of the solid component of the polymeric liquid crystal composition. When the content of the polymeric liquid crystal compound is within the above range, it is advantageous from the viewpoint of the orientation of the obtained liquid crystal cured film.

[0151] The polymeric liquid crystal composition used in the formation of the horizontally oriented liquid crystal cured film may also include, in addition to the polymeric liquid crystal compound, additives such as solvents, polymerization initiators, leveling agents, antioxidants, and photosensitizers. Examples of these components include those previously exemplified as components that can be used in the vertically oriented liquid crystal cured film; only one of each may be used, or two or more may be used in combination.

[0152] The polymeric liquid crystal composition used in the formation of horizontally oriented liquid crystal cured films can be obtained by stirring the polymeric liquid crystal compound, a solvent, a photopolymerization initiator, and other components other than the polymeric liquid crystal compound at a specified temperature.

[0153] It should be noted that, in this invention, the second optical anisotropy layer preferably satisfies the following formula (4).

[0154] 5nm≤R”40(550)≤30nm (4) In equation (4), R”40 (550) represents the phase difference value when the second optical anisotropic layer is tilted by 40 degrees at a wavelength of 550 nm. R”40 (550) is more preferably 28 nm or less, and even more preferably 26 nm or less. By satisfying the above numerical range, when the optical laminate of the present invention is used in an image display device, it is possible to obtain the effect of further preventing light leakage and color shift when visually recognizing the black display from the tilt direction.

[0155] [Optical laminate and manufacturing method of optical laminate] In this invention, the optical laminate includes a first optical anisotropic layer and a second optical anisotropic layer. In one embodiment of this invention, when the first optical anisotropic layer and the second optical anisotropic layer are stacked, as shown... Figure 1 or Figure 2 The example shown is an optical laminate 2 that sequentially comprises a first optical anisotropic layer 4 and a second optical anisotropic layer 5. The first optical anisotropic layer can be, for example, a cured polymeric liquid crystal composition (vertically oriented liquid crystal cured film) obtained by curing a polymeric liquid crystal compound in a state oriented vertically relative to the film plane. Furthermore, the second optical anisotropic layer, as described above, can be, for example, a cured layer of a polymeric liquid crystal composition obtained by curing a stretched film, a substrate, or a polymeric liquid crystal compound in a state oriented horizontally relative to the film plane.

[0156] In this invention, for example, a laminate having a first optical anisotropy layer directly on a second optical anisotropy layer can be manufactured by the following process: forming a coating of a polymeric liquid crystal composition for forming a vertically oriented liquid crystal curing film containing a polymeric liquid crystal compound on a stretching film (second optical anisotropy), and forming a vertically oriented liquid crystal curing film from the coating film (hereinafter also referred to as the "vertically oriented liquid crystal curing film forming process").

[0157] In this invention, with regard to optical laminates, for example, a laminate having a first optical anisotropy layer directly on a second optical anisotropy layer can be manufactured by the following method, the method comprising: The process of forming a coating film of a polymeric liquid crystal composition for forming a horizontally oriented liquid crystal curable film containing a polymeric liquid crystal compound, and forming a horizontally oriented liquid crystal curable film from the coating film (hereinafter also referred to as the "horizontally oriented liquid crystal curable film forming process"); and a vertically oriented liquid crystal curable film forming process.

[0158] In this invention, when the second optical anisotropic layer of the optical laminate is formed from a horizontally aligned liquid crystal curable film, it is preferable to include a step of forming a coating of a horizontally aligned film forming composition and forming a horizontally aligned film from the coating (hereinafter also referred to as the "horizontal alignment film forming step") before forming the horizontally aligned liquid crystal curable film. Preferably, the horizontal alignment film forming step and the horizontally aligned liquid crystal curable film forming step are performed sequentially. By using a manufacturing method including the horizontal alignment film forming step, an optical anisotropic layer formed from a horizontally aligned liquid crystal curable film formed on a horizontally aligned film is obtained.

[0159] In the process of forming a horizontally aligned liquid crystal curable film, the horizontally aligned liquid crystal curable film can be manufactured, for example, by the following method, which includes: The process of coating a polymeric liquid crystal composition for forming a horizontally oriented liquid crystal curing film onto a substrate or an oriented film to obtain a coating film; The process of drying the aforementioned coating to form a dry coating film; and, The process of forming a horizontally oriented liquid crystal curing film by irradiating a dry coating with active energy rays.

[0160] The coating film of the polymeric liquid crystal composition can be formed, for example, by coating a polymeric liquid crystal composition for forming a horizontally aligned liquid crystal curing film onto a substrate or an alignment film described later. The substrate exemplified in the second optical anisotropy layer can be used as the substrate.

[0161] Methods for coating polymeric liquid crystal compositions onto substrates include known methods such as spin coating, extrusion, gravure coating, die coating, squeegee coating, coater coating, and printing methods such as flexographic printing.

[0162] Next, the solvent is removed by drying or the like, forming a dried coating film. Examples of drying methods include natural drying, ventilation drying, heating drying, and reduced pressure drying. At this time, by heating the coating film obtained from the polymeric liquid crystal composition, the solvent can be removed from the coating film while the polymeric liquid crystal compound is oriented horizontally relative to the coating film plane. The heating temperature of the coating film can be appropriately determined considering the polymeric liquid crystal compound used and the material of the substrate to which the coating film is formed, but in order to transform the polymeric liquid crystal compound into a liquid crystal phase, a temperature above the liquid crystal phase transition temperature is generally required. In order to remove the solvent contained in the polymeric liquid crystal composition while simultaneously making the polymeric liquid crystal compound horizontally oriented, for example, the temperature can be heated to near or above the liquid crystal phase transition temperature (smectic phase transition temperature or nematic phase transition temperature) of the polymeric liquid crystal compound contained in the aforementioned polymeric liquid crystal composition.

[0163] It should be noted that the liquid crystal phase transition temperature can be measured using, for example, a polarizing microscope equipped with a temperature stage, a differential scanning calorimeter (DSC), or a thermogravimetric differential calorimeter (TG-DTA). Furthermore, when two or more polymeric liquid crystal compounds are used in combination as polymeric liquid crystal compounds, the aforementioned phase transition temperature refers to the temperature measured using a mixture of polymeric liquid crystal compounds obtained by mixing all the polymeric liquid crystal compounds constituting the polymeric liquid crystal composition at the same ratio as the composition in the polymeric liquid crystal composition, in the same manner as when using a single polymeric liquid crystal compound. It should be noted that it is known that the liquid crystal phase transition temperature of the polymeric liquid crystal compound in the aforementioned polymeric liquid crystal composition is generally lower than the liquid crystal phase transition temperature of the polymeric liquid crystal compound monomer.

[0164] The heating time can be appropriately determined according to the heating temperature, the type of polymeric liquid crystal compound used, the type of solvent, its boiling point and amount, etc., and is usually 15 seconds to 10 minutes, preferably 0.5 to 5 minutes.

[0165] Solvent removal from the coating film can be performed simultaneously with heating to above the liquid crystal phase transition temperature of the polymerizable liquid crystal compound, or independently; however, simultaneous removal is preferred from the viewpoint of improving productivity. Before heating to above the liquid crystal phase transition temperature of the polymerizable liquid crystal compound, a pre-drying step can be provided to adequately remove the solvent from the coating film under conditions that do not cause polymerization of the polymerizable liquid crystal compound contained in the coating film obtained from the polymerizable liquid crystal composition. Examples of drying methods in the pre-drying step include natural drying, ventilation drying, heating drying, and reduced pressure drying. The drying temperature (heating temperature) in this drying step can be appropriately determined according to the type of polymerizable liquid crystal compound used, the type of solvent, its boiling point, and its amount.

[0166] Next, in the obtained dried coating film, the polymerizable liquid crystal compound is polymerized while maintaining its horizontal orientation, thereby forming a horizontally oriented liquid crystal cured film. Examples of polymerization methods include thermal polymerization and photopolymerization, but photopolymerization is preferred from the viewpoint of easy control of the polymerization reaction. In photopolymerization, the light irradiating the dried coating film can be appropriately selected based on the type of polymerization initiator contained in the dried coating film, the type of polymerizable liquid crystal compound (especially the type of polymeric groups possessed by the polymerizable liquid crystal compound), and their amount. Specific examples include light selected from the group consisting of visible light, ultraviolet light, infrared light, X-rays, alpha rays, beta rays, and gamma rays, and active electron beams. Among these, ultraviolet light is preferred from the viewpoint of easy control of the polymerization reaction and the ability to use a device widely used in the art as a photopolymerization apparatus. It is preferable to pre-select the type of polymerizable liquid crystal compound and polymerization initiator contained in the polymerizable liquid crystal composition in a manner suitable for photopolymerization using ultraviolet light. Furthermore, during polymerization, the polymerization temperature can be controlled by simultaneously cooling the dried coating using appropriate cooling methods and then irradiating it with light. If the polymerization of the polymerizable liquid crystal compound is carried out at a lower temperature using such cooling methods, a horizontally oriented liquid crystal cured film can be appropriately formed even when using a substrate with low heat resistance. Additionally, the polymerization reaction can be promoted by increasing the polymerization temperature, provided that adverse effects caused by heat during light irradiation (such as substrate deformation due to heat) do not occur. During photopolymerization, a patterned cured film can also be obtained by masking, developing, etc.

[0167] Examples of light sources for the aforementioned active energy rays include low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, xenon lamps, halogen lamps, carbon arc lamps, tungsten lamps, gallium lamps, excimer lasers, LED light sources emitting light in the wavelength range of 380–440 nm, chemical lamps, black light lamps, microwave-excited mercury lamps, and metal halide lamps.

[0168] Ultraviolet radiation intensity is typically 10–3,000 mW / cm². 2 The intensity of ultraviolet irradiation is preferably within the wavelength range effective for activating photopolymerization initiators. The irradiation time is typically 0.1 seconds to 10 minutes, preferably 0.1 seconds to 5 minutes, more preferably 0.1 seconds to 3 minutes, and even more preferably 0.1 seconds to 1 minute. When irradiated once or multiple times at such an intensity, the cumulative light intensity is 10 to 3,000 mJ / cm². 2 Preferably, it is 50–2,000 mJ / cm². 2 More preferably 100–1,000 mJ / cm 2 .

[0169] Since it can improve the orientation order of the horizontally oriented liquid crystal curing film, it is preferable in this invention that the coating of the polymeric liquid crystal composition for forming the horizontally oriented liquid crystal curing film is formed on a horizontally oriented film having orientation control force in the horizontal direction relative to the plane of the obtained liquid crystal curing film. Therefore, in the optical laminate of this invention, it is preferable that a second optical anisotropy layer is formed on the horizontally oriented film, and the horizontally oriented liquid crystal curing film is sequentially included.

[0170] It should be noted that the orientation control force of the orientation film can be arbitrarily adjusted by the type of orientation film, surface condition, friction conditions, etc. When the orientation film is formed by photo-oriented polymer, it can be arbitrarily adjusted by polarized light irradiation conditions, etc.

[0171] As a horizontal alignment film, it is preferable to have solvent resistance that prevents dissolution due to coating of the polymeric liquid crystal composition, and heat resistance for solvent removal and heat treatment for the orientation of the polymeric liquid crystal compound (described later). Examples of alignment films include alignment films containing an alignment polymer, photoalignment films, grooved alignment films with raised or recessed patterns or multiple grooves on the surface, and stretched films stretched along the alignment direction. From the viewpoint of the accuracy and quality of the alignment angle, photoalignment films are preferred.

[0172] Examples of oriented polymers include polyamides having intramolecular amide bonds, gelatin-like substances, polyimides having intramolecular imide bonds and their hydrolysates such as polyamic acid, polyvinyl alcohol, alkyl-modified polyvinyl alcohol, polyacrylamide, polyoxazole, polyethyleneimine, polystyrene, polyvinylpyrrolidone, polyacrylic acid, and polyacrylates. Polyvinyl alcohol is preferred. Oriented polymers can be used alone or in combination of two or more.

[0173] Alignment films containing oriented polymers can typically be obtained by: coating a composition (hereinafter sometimes referred to as "oriented polymer composition") obtained by dissolving the oriented polymer in a solvent onto a substrate, and then removing the solvent; or by coating the oriented polymer composition onto a substrate, removing the solvent, and then rubbing (rubbing method). Examples of solvents include those previously exemplified as solvents that can be used in polymeric liquid crystal compositions.

[0174] The concentration of the oriented polymer in the oriented polymer composition is only required to be within the range where the oriented polymer material can be completely dissolved in the solvent. Relative to the solution, it is preferably 0.1 to 20% when converted to solid content, and more preferably about 0.1 to 10%.

[0175] As an orientation polymer composition, commercially available orientation film materials can be used directly. Examples of commercially available orientation film materials include SUNEVER (registered trademark, manufactured by Nissan Chemical Industries, Ltd.) and Optomer (registered trademark, manufactured by JSR Corporation).

[0176] As a method for coating an oriented polymer composition onto a substrate, the same method as the method exemplified above as a method for coating a polymeric liquid crystal composition onto a substrate can be cited.

[0177] Methods for removing solvents contained in oriented polymer compositions include natural drying, ventilation drying, heating drying, and vacuum drying.

[0178] To impart orientation control force to an alignment film, a friction treatment (friction method) can be performed as needed. One method for imparting orientation control force using the friction method is to bring a film of an orientation polymer, formed on the surface of a substrate by coating an orientation polymer composition onto a substrate and then annealing it, into contact with a friction roller wound with a friction cloth and rotating. If masking is applied during the friction treatment, multiple regions (patterns) with different orientation directions can also be formed on the alignment film.

[0179] As a preferred embodiment of the present invention, the horizontally aligned film is a photo-aligned film formed from a polymer having (meth)acryloyl groups. When the horizontally aligned film has polymeric groups that are similar to or the same as those in the polymeric liquid crystal compound constituting the horizontally aligned liquid crystal cured film, there is a tendency to further improve the adhesion between the horizontally aligned film and the horizontally aligned liquid crystal cured film. Therefore, it is preferred that the horizontally aligned film is formed from a polymer having (meth)acryloyl groups, and the horizontally aligned liquid crystal cured film is formed from a polymeric liquid crystal composition containing a polymeric liquid crystal compound having (meth)acryloyl groups.

[0180] Photoalignment films are typically obtained by coating a composition (hereinafter also referred to as a "composition for photoalignment film formation") containing a polymer or monomer having photoreactive groups onto a substrate, removing the solvent, and then irradiating it with polarized light (preferably polarized UV light). It is advantageous in the case of photoalignment films that the direction of the alignment control force can be arbitrarily controlled by selecting the polarization direction of the irradiated polarized light.

[0181] A photoreactive group refers to a group that generates liquid crystal alignment ability through light irradiation. Specifically, it includes photoreactive groups that participate in molecular orientation-inducing or isomerization reactions, dimerization reactions, photocrosslinking reactions, or photodecomposition reactions that occur through light irradiation, thus becoming the source of liquid crystal alignment ability. Among these, groups participating in dimerization reactions or photocrosslinking reactions are preferred from the perspective of excellent orientation. As a photoreactive group, it is preferred to have a group having unsaturated bonds, especially double bonds, and particularly preferred to have a group having at least one selected from the group consisting of carbon-carbon double bonds (C=C bond), carbon-nitrogen double bonds (C=N bond), nitrogen-nitrogen double bonds (N=N bond), and carbon-oxygen double bonds (C=O bond).

[0182] Examples of photoreactive groups with C=C bonds include vinyl, polyenyl, stilbazole, stilbazolium, chalcone, and cinnamoyl groups. Examples of photoreactive groups with C=N bonds include groups with aromatic Schiff bases and aromatic hydrazones. Examples of photoreactive groups with N=N bonds include azophenyl, azonaphthyl, aromatic heterocyclic azo, diazo, formazan, and groups with an azobenzene oxide structure. Examples of photoreactive groups with C=O bonds include benzophenone, coumarin, anthraquinone, and maleimide groups. These groups can have substituents such as alkyl, alkoxy, aryl, allyloxy, cyano, alkoxycarbonyl, hydroxyl, sulfonic acid, and haloalkyl groups.

[0183] Among these, photoreactive groups that participate in the photodimerization reaction are preferred. Considering the need for less polarized light irradiation required for photoorientation and the ease of obtaining photoorientation films with excellent thermal and time stability, azo, cinnamoyl, and chalcone groups are preferred. As polymers with photoreactive groups, polymers with azo or cinnamoyl groups are preferred. From the viewpoint of improving the adhesion between the horizontally oriented film and the horizontally oriented liquid crystal curable film, polymers with cinnamoyl groups, where the end of the polymer side chain is a cinnamic acid structure, are particularly preferred.

[0184] By coating a photo-alignment film forming composition onto a substrate, a photo-alignment induction layer can be formed on the substrate. As a solvent included in the composition, the same solvents exemplified above as solvents that can be used in polymeric liquid crystal compositions can be appropriately selected based on the solubility of the polymer or monomer having photoreactive groups.

[0185] The content of the polymer or monomer having photoreactive groups in the composition for forming a photoalignment film can be appropriately adjusted according to the type of polymer or monomer and the thickness of the target photoalignment film. Preferably, it is set to at least 0.2% by mass, more preferably in the range of 0.3% to 10% by mass relative to the mass of the composition for forming a photoalignment film. The composition for forming a photoalignment film may also contain polymers such as polyvinyl alcohol and polyimide, and photosensitizers, without significantly impairing the properties of the photoalignment film.

[0186] As a method for coating a composition for forming a photo-aligned film onto a substrate, the same method as the method for coating an orientation polymer composition onto a substrate can be cited. As a method for removing solvent from the coated composition for forming a photo-aligned film, for example, natural drying, ventilation drying, heating drying, and reduced pressure drying can be cited.

[0187] When irradiating with polarized light, the polarized UV light can be directly irradiated onto the material obtained after removing the solvent from the composition for forming a photo-alignment film coated on a substrate, or it can be irradiated from the substrate side, allowing the polarized light to pass through. Furthermore, it is particularly preferable that the polarized light is substantially parallel light. The wavelength of the irradiated polarized light is preferably a wavelength in the region where the photoreactive groups of the polymer or monomer having photoreactive groups can absorb light energy. Specifically, UV (ultraviolet) light in the wavelength range of 250 to 400 nm is particularly preferred. Examples of light sources used for this polarized light irradiation include xenon lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, KrF, ArF, and other ultraviolet lasers, with high-pressure mercury lamps, ultra-high-pressure mercury lamps, and metal halide lamps being more preferred. Among these, high-pressure mercury lamps, ultra-high-pressure mercury lamps, and metal halide lamps are preferred because of the high luminous intensity of ultraviolet light at a wavelength of 313 nm. By irradiating the light from the aforementioned light source through a suitable polarizer, polarized UV light can be irradiated. As the polarizer, polarizing filters, polarizing prisms such as Glan-Thompson and Glan-Taylor, and wire grid type polarizers can be used.

[0188] It should be noted that if the area is shielded during rubbing or polarized light irradiation, multiple regions (patterns) with different liquid crystal orientations can be formed.

[0189] Groove-aligned films are films with raised or recessed patterns or multiple grooves (slots) on their surface. When a polymerizable liquid crystal compound is coated onto a film having multiple linear grooves arranged at equal intervals, the liquid crystal molecules will align along the direction of the grooves.

[0190] Examples of methods for obtaining grooved oriented films include: exposing the surface of a photosensitive polyimide film through an exposure mask with a patterned slit, followed by development and rinsing to form a raised or recessed pattern; forming a layer of UV-curable resin before curing on a plate-shaped template with grooves on its surface, transferring the formed resin layer to a substrate, and then curing it; and pressing a roll-shaped template with multiple grooves onto a film of UV-curable resin before curing formed on a substrate to form a raised or recessed pattern, followed by curing; and so on.

[0191] The thickness of the alignment film (an alignment film containing an alignment polymer or a photoalignment film) is typically 100–5000 nm, preferably 100–1000 nm, more preferably 100–500 nm, further preferably 100–300 nm, and particularly preferably 100–250 nm. When the thickness of the alignment film is within the above range, it provides sufficient horizontal alignment control and, moreover, is less prone to cohesive failure in the alignment film within the laminate.

[0192] In this invention, when the first optical anisotropic layer of the optical laminate is formed from a vertically oriented liquid crystal curing film, Regarding vertically oriented liquid crystal curing films, for example, an optical laminate having a first optical anisotropy layer directly on a second optical anisotropy layer can be manufactured by a method that includes the following steps in the vertically oriented liquid crystal curing film forming process: The process of coating a polymeric liquid crystal composition for forming a vertically oriented liquid crystal curing film onto a stretching film (second optical anisotropy layer) to obtain a coating film; The process of drying the aforementioned coating to form a dry coating film; and, The process of forming a vertically oriented liquid crystal curing film by irradiating a dry coating with active energy rays.

[0193] The formation of a coating film of a polymeric liquid crystal composition can be performed, for example, by coating a vertically oriented polymeric liquid crystal composition for forming a liquid crystal curing film onto a stretched film. As a coating method for the polymeric liquid crystal composition, methods similar to those used in the manufacturing method of a horizontally oriented liquid crystal curing film can be cited.

[0194] Regarding vertically oriented liquid crystal curing films, for example, an optical laminate having a first optical anisotropy layer directly on a second optical anisotropy layer can be manufactured by a method that includes the following steps in the vertically oriented liquid crystal curing film forming process: The process of coating a vertically oriented liquid crystal curing film by coating a polymeric liquid crystal composition for forming a vertically oriented liquid crystal curing film onto a horizontally oriented liquid crystal curing film (second optical anisotropy layer) to obtain a coating film; The process of drying the aforementioned coating to form a dry coating film; and, The process of forming a vertically oriented liquid crystal curing film by irradiating a dry coating with active energy rays.

[0195] The formation of a coating film of a polymeric liquid crystal composition can be performed, for example, by coating a horizontally oriented liquid crystal curing film with a polymeric liquid crystal composition for forming a vertically oriented liquid crystal curing film. As a coating method for the polymeric liquid crystal composition, methods similar to those used in the manufacturing method of a horizontally oriented liquid crystal curing film can be cited.

[0196] Furthermore, the formation of the coating film of the polymeric liquid crystal composition can be performed, for example, by coating a polymeric liquid crystal composition for forming a vertically oriented liquid crystal curing film onto the aforementioned substrate. The substrate exemplified in the second optical anisotropy layer can be used as the substrate.

[0197] It should be noted that, in this invention, as long as it does not affect the effect of the invention, the horizontally oriented liquid crystal curing film and the vertically oriented liquid crystal curing film can be stacked with other layers in between. For example, an adhesive layer can be considered as such other layer. When the optical laminate of the present invention includes an adhesive layer, the thickness of the adhesive layer is preferably 0.1 to 30 μm, more preferably 0.5 to 20 μm.

[0198] Examples of adhesive layers include pressure-sensitive adhesives and energy-cured adhesives. Among these, acrylic adhesives, epoxy adhesives, and urethane adhesives are preferred due to their high transparency and excellent heat resistance.

[0199] Furthermore, in this invention, a cured resin layer, a hard coating layer, or the like, intended to improve or enhance the mechanical strength of the liquid crystal cured film, can be used as the aforementioned other layers. When the optical laminate of this invention includes such other layers between the horizontally aligned liquid crystal cured film and the vertically aligned liquid crystal cured film, the thickness of these other layers is preferably 0.1 to 4 μm, more preferably 0.5 to 3 μm. When the optical laminate of this invention includes such other layers between the horizontally aligned liquid crystal cured film and the vertically aligned liquid crystal cured film, the other layers can be formed after the horizontally aligned liquid crystal cured film is formed, and then a coating of the polymeric liquid crystal composition for forming the vertically aligned liquid crystal cured film can be formed on the aforementioned other layers.

[0200] The aforementioned cured resin layer can be formed from, for example, acrylic resin, methacrylic resin, epoxy resin, oxetane resin, urethane resin, melamine resin, etc. By providing a cured resin layer, even if the liquid crystal cured film formed adjacent to the cured resin layer is a thin film, the cured resin layer can serve as a protective layer or reinforcing layer to fully compensate for the strength of the liquid crystal cured film.

[0201] After forming a coating of the polymeric liquid crystal composition, the solvent is removed by drying or the like, thereby forming a dried coating. Examples of drying methods include natural drying, ventilation drying, heating drying, and reduced pressure drying. From a productivity perspective, heating drying is preferred, and the heating temperature in this case is preferably high enough to remove the solvent and above the phase transition temperature of the polymeric liquid crystal compound. Regarding the steps and conditions in this process, examples can be given that are the same as those used in methods for manufacturing horizontally aligned liquid crystal cured films.

[0202] The obtained dried coating is irradiated with active energy rays (more specifically, ultraviolet light, etc.), and the polymerizable liquid crystal compound is polymerized while maintaining its orientation perpendicular to the coating plane, thereby forming a vertically oriented liquid crystal cured film. As a polymerization method, methods similar to those used in the manufacture of horizontally oriented liquid crystal cured films can be cited.

[0203] In this invention, the optical laminate may also be configured such that a second optical anisotropic layer is disposed on the first optical anisotropic layer.

[0204] A laminate obtained by disposing a second optical anisotropic layer on a first optical anisotropic layer can be manufactured by the following method, which includes the following steps: The process of coating a polymeric liquid crystal composition for forming a vertically oriented liquid crystal curing film onto a substrate to obtain a coating film; The process of drying the aforementioned coating to form a dry coating film; The process of forming a vertically oriented liquid crystal curing film (first optical anisotropy layer) by irradiating a dry coating with active energy rays; The process of coating a horizontally oriented liquid crystal curing film onto the aforementioned vertically oriented liquid crystal curing film to obtain a coating film; The process of drying the aforementioned coating to form a dry coating film; and, The process of forming a horizontally oriented liquid crystal curing film (second optical anisotropy layer) by irradiating a dry coating with active energy rays.

[0205] [Optical laminate with protective film and method for manufacturing optical laminate with protective film] The process of bonding the optical laminate 2 to the protective film 3 (the manufacturing process of the optical laminate with a protective film) can be referred to, for example, by referring to Figure 3 This is done using a pair of rollers (lamination rollers) 6, 6. From a manufacturing efficiency point of view, this method is particularly advantageous when the optical laminate 2 and the protective film 3 are in the form of long strips.

[0206] Therefore, it is preferable that both the optical laminate 2 and the protective film 3 supplied in the manufacturing process of the optical laminate with protective film are elongated strips.

[0207] The length of the elongated optical laminate 2 and the protective film 3 is, for example, 100 to 20,000 m, preferably 1,000 to 10,000 m. In addition, the width of the elongated optical laminate 2 and the protective film 3 is, for example, 0.5 to 3 m, preferably 1 to 2.5 m.

[0208] Regarding the bonding of the optical laminate 2 and the protective film 3, for example, the long strip of optical laminate 2 is continuously transported, and the long strip of protective film 3 is continuously transported. The protective film 3 is laminated on one side of the optical laminate 2 and passed between a pair of bonding rollers 6, 6 for clamping. In this way, an optical laminate 1 with a protective film is produced by bonding the two films.

[0209] The MD direction (transport direction) of the optical laminate 2 and the MD direction (transport direction) of the protective film 3 are usually parallel. Parallelism means that the angle between the MD direction of the optical laminate 2 and the MD direction of the protective film 3 is 0 degrees ± 5 degrees, preferably 0 degrees ± 2 degrees.

[0210] By passing the optical laminate 2 and the protective film 3 into a pair of bonding rollers 6, the laminate is pushed from above and below, thus the two films are tightly bonded.

[0211] When the protective film 3 is composed of a substrate film and an adhesive layer laminated thereon, the protective film 3 is laminated on one side of the optical laminate 2 and passed between a pair of laminating rollers 6, 6, so that the adhesive layer of the protective film 3 is in contact with the aforementioned one side of the optical laminate 2. Alternatively, before laminating the protective film 3 and the optical laminate 2, the laminating surfaces of at least one of the protective film 3 and the optical laminate 2 may be subjected to surface activation treatments such as plasma treatment, corona treatment, ultraviolet irradiation treatment, flame treatment, or saponification treatment.

[0212] In the bonding process using a pair of bonding rollers 6, 6, the pressure (clamping pressure) applied to the laminate of the protective film 3 and the optical laminate 2 is, for example, 0.01 to 0.5 MPa, or 0.05 to 0.3 MPa. The bonding rollers 6, 6 can be conventionally known rollers with surfaces made of metal (including alloys such as SUS) or rubber.

[0213] As a configuration of an optical laminate with a protective film, a laminate having a protective film, a first optical anisotropic layer, and a second optical anisotropic layer sequentially can be formed by laminating a protective film on the surface of the first optical anisotropic layer opposite to the second optical anisotropic layer. Alternatively, a laminate having a protective film, a second optical anisotropic layer, and a first optical anisotropic layer sequentially can be formed by laminating a protective film on the surface of the second optical anisotropic layer opposite to the first optical anisotropic layer. The protective film can be laminated on either the surface of the first optical anisotropic layer opposite to the second optical anisotropic layer or the surface of the second optical anisotropic layer opposite to the first optical anisotropic layer in the optical laminate. However, there is a possibility that the stability may be reduced by bringing the adhesive layer constituting the protective film into contact with the liquid crystal curing film. Therefore, it is preferable to laminate it on the surface of the optical anisotropic layer that is not a liquid crystal curing film.

[0214] In the optical laminate with protective film of the present invention, it is preferable to have a protective film laminated on the surface of the second optical anisotropy layer opposite to the first optical anisotropy layer, wherein the first optical anisotropy layer is a vertically oriented liquid crystal curing film and the second optical anisotropy layer is a stretching film. This is because particularly excellent storage stability can be achieved when the manufactured optical laminate with protective film is stored in a wound form.

[0215] [Polarizing plate with protective film] The present invention includes a polarizing plate with a protective film comprising an optical laminate with a protective film and a polarizing film of the present invention.

[0216] A polarizing film is a film that has a polarizing function. Examples include a stretched film containing an anisotropically absorbent pigment, and a film coated with an anisotropically absorbent pigment, which can be used as a polarizer. Examples of anisotropically absorbent pigments include, for instance, dichroic pigments.

[0217] For a polarizer comprising a stretched film containing an anisotropically absorbent pigment, it is typically manufactured by clamping at least one side of the polarizer with a transparent protective film via an adhesive, the polarizer being manufactured by the following steps: uniaxial stretching of a polyvinyl alcohol (PVA) resin film; dyeing the PVA resin film with a dichroic pigment to induce the adsorption of the dichroic pigment; treating the PVA resin film containing the dichroic pigment with an aqueous boric acid solution; and washing with water after treatment with the aqueous boric acid solution.

[0218] Polyvinyl alcohol-based resins are obtained by saponifying polyvinyl acetate-based resins. Besides polyvinyl acetate as a homopolymer of vinyl acetate, copolymers of vinyl acetate with other monomers that can be copolymerized with it can also be used as polyvinyl acetate-based resins. Examples of other monomers that can be copolymerized with vinyl acetate include, for example, unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, and acrylamides containing ammonium groups.

[0219] The degree of saponification of polyvinyl alcohol (PVA) resins is typically around 85–100 mol%, preferably 98 mol% or higher. PVA resins can be modified; for example, aldehyde-modified PVA formal or PVA acetal can be used. The degree of polymerization of PVA resins is typically around 1,000–10,000, preferably in the range of 1,500–5,000.

[0220] Films made from such polyvinyl alcohol (PVA) resins can be used as preforms for polarizing films. There are no particular limitations on the method for preparing the film from the PVA resin; known methods can be used. The thickness of the PVA preform can be, for example, approximately 10–150 μm.

[0221] Uniaxial stretching of polyvinyl alcohol (PVA) resin films can be performed before, during, or after dyeing with dichroic pigments. When uniaxial stretching is performed after dyeing, it can be done before or during boric acid treatment. Alternatively, uniaxial stretching can be performed at multiple stages. Uniaxial stretching can be performed between rollers with different circumferential speeds, or it can be done using heated rollers. Furthermore, uniaxial stretching can be dry stretching performed in the atmosphere or wet stretching performed while the PVA resin film is swollen with a solvent. The stretching ratio is typically around 3 to 8 times.

[0222] The dyeing of polyvinyl alcohol-based resin films based on dichroic pigments can be carried out, for example, by impregnating the polyvinyl alcohol-based resin film in an aqueous solution containing dichroic pigments.

[0223] Specifically, iodine and dichroic organic dyes can be used as dichroic pigments. Examples of dichroic organic dyes include direct dichroic dyes formed from diazide compounds such as Direct Red 39 (CI), and direct dichroic dyes formed from compounds such as triazo and tetraazo. For polyvinyl alcohol-based resin films, it is preferable to pre-treat them by immersion in water before dyeing.

[0224] When using iodine as a dichroic dye, the dyeing method typically involves impregnating a polyvinyl alcohol-based resin film in an aqueous solution containing iodine and potassium iodide. The iodine content in this aqueous solution is typically about 0.01 to 1 part by weight relative to 100 parts by weight of water. The potassium iodide content is typically about 0.5 to 20 parts by weight relative to 100 parts by weight of water. The temperature of the aqueous solution used for dyeing is typically about 20 to 40°C. The impregnation time (dyeing time) in this aqueous solution is typically about 20 to 1,800 seconds.

[0225] On the other hand, when using dichroic organic dyes as dichroic pigments, a common dyeing method is to impregnate a polyvinyl alcohol-based resin film in an aqueous solution containing the water-soluble dichroic dye. The content of the dichroic organic dye in this aqueous solution is typically 1 × 10⁻¹⁰ parts by mass relative to 100 parts by mass of water. -4 Approximately 10 parts by weight, preferably 1×10 -3 ~1 part by weight, more preferably 1×10 -3 ~1×10 -2 Parts by weight. This aqueous solution may contain inorganic salts such as sodium sulfate as dyeing auxiliaries. The temperature of the aqueous solution of dichroic dyes used for dyeing is usually around 20–80°C. In addition, the immersion time (dyeing time) in this aqueous solution is usually around 10–1,800 seconds.

[0226] Boric acid treatment following dyeing with dichroic pigments is typically performed by immersing the dyed polyvinyl alcohol-based resin film in an aqueous boric acid solution. The boric acid content in this aqueous solution is typically about 2 to 15 parts by weight relative to 100 parts by weight of water, preferably 5 to 12 parts by weight. When iodine is used as the dichroic pigment, the aqueous boric acid solution preferably contains potassium iodide, typically at a content of about 0.1 to 15 parts by weight relative to 100 parts by weight of water, preferably 5 to 12 parts by weight. The immersion time in the aqueous boric acid solution is typically about 60 to 1,200 seconds, preferably 150 to 600 seconds, more preferably 200 to 400 seconds. The temperature for boric acid treatment is typically above 50°C, preferably 50 to 85°C, more preferably 60 to 80°C.

[0227] Typically, boric acid-treated polyvinyl alcohol (PVA) resin membranes can be washed with water. This washing process can be performed, for example, by immersing the boric acid-treated PVA resin membrane in water. The water temperature during washing is usually around 5–40°C. The immersion time is typically around 1–120 seconds.

[0228] The polarizer can be dried after washing to obtain a polarizing film. Drying can be performed using, for example, a hot air dryer or a far-infrared heater. The drying temperature is typically around 30–100°C, preferably 50–80°C. The drying time is typically around 60–600 seconds, preferably 120–600 seconds. Drying reduces the moisture content of the polarizer to a practical level. This moisture content is typically around 5–20% by mass, preferably 8–15% by mass. If the moisture content is below 5% by mass, the polarizer loses its flexibility, and may be damaged or break after drying. Furthermore, if the moisture content is above 20% by mass, the thermal stability of the polarizer may deteriorate.

[0229] The thickness of the polarizer obtained by subjecting the polyvinyl alcohol-based resin film to uniaxial stretching, dyeing based on dichroic pigments, boric acid treatment, washing and drying as described above is preferably 5 to 40 μm.

[0230] Examples of films made by coating with anisotropic absorbent pigments include films coated with a composition containing a dichroic pigment having liquid crystal properties, or films containing a dichroic pigment and a polymerizable liquid crystal. Preferably, the film has a protective film on one or both sides. Examples of such a protective film include the same resin film exemplified above as a substrate used in the manufacture of horizontally oriented liquid crystal cured films.

[0231] The thinner the film coated with an anisotropic pigment, the better; however, if it is too thin, the strength decreases and the processability tends to be poor. The thickness of the film is usually less than 20 μm, preferably less than 5 μm, and more preferably 0.5 to 3 μm.

[0232] Specifically, as a film coated with an anisotropic pigment, examples include the film described in Japanese Patent Application Publication No. 2012-33249.

[0233] At least one side of the polarizer obtained in the manner described above may be laminated with a transparent protective film, for example, through an adhesive layer. The same transparent protective film as the resin film exemplified above, which is used as a substrate in the manufacture of a liquid crystal curable film, can be used as the transparent protective film.

[0234] The polarizing plate with protective film of the present invention is composed of the optical laminate with protective film of the present invention and a polarizing film. For example, the optical laminate with protective film of the present invention and the polarizing film are laminated through an adhesive layer or the like to obtain the polarizing plate with protective film of the present invention.

[0235] In one embodiment of the present invention, when the optical laminate with a protective film is laminated with a polarizing film, such as... Figure 4 and Figure 5As illustrated, the laminate, which sequentially includes a polarizing film 7 and an optical laminate 1 with a protective film, forms a polarizing plate 8 with a protective film. In the polarizing plate 8 with a protective film, when the polarizing film 7 and the optical laminate 1 with a protective film are laminated, it is possible to... Figure 4 As shown, the polarizing film 7 is stacked on the surface of the first optical anisotropy layer 4, which is opposite to the second optical anisotropy layer 5, in the optical laminate 1 with a protective film. Alternatively, it can be done as follows: Figure 5 The polarizing film 7 is stacked on the surface of the second optical anisotropy layer 5, which is opposite to the first optical anisotropy layer 4, in the optical laminate 1 with a protective film. At this time, the optical laminate 1 with the protective film and the polarizing film 7 can be bonded together by means of an adhesive layer to obtain the polarizing plate with a protective film according to the present invention.

[0236] As an adhesive layer for bonding the polarizing film to the optical laminate with a protective film, the same layer as the aforementioned other layers used to bond the horizontally oriented liquid crystal curing film to the vertically oriented liquid crystal curing film can be used.

[0237] In this invention, as a pretreatment for bonding the polarizing film to the optical laminate with a protective film, it is preferable to perform surface treatments such as corona treatment or plasma treatment on the surface of the optical laminate that is bonded to the polarizing film, and more preferably to perform corona treatment.

[0238] The polarizing plate with a protective film of the present invention may also have the same configuration as conventional polarizing plates, polarizing films, and retardation films. Examples of such configurations include adhesive layers (sheets) for attaching the polarizing plate to display elements such as liquid crystal display devices, and protective films used to protect the surfaces of polarizing films and liquid crystal curing films from damage or contamination.

[0239] In this invention, the protective film included in the optical laminate with protective film and the polarizing plate with protective film is used for peeling when applied to a display device, as described later. Therefore, it is preferable that it can be easily peeled off from the optical laminate with protective film and the polarizing plate with protective film. The adhesive force of the protective film can be defined as the adhesive force to the SUS when the adhered object is set as SUS, and can be determined according to JIS Z 0237 (Test Method for Adhesive Tape / Sheet), preferably 0.20 N / 25 mm or less, more preferably 0.15 N / 25 mm or less. In addition, the peel force of the protective film from the adhered object can be determined according to JIS K7161:1994 and JIS K7127:1999, preferably 0.15 N / 25 mm or less, more preferably 0.10 N / 25 mm or less. When the adhesive force of the protective film to SUS and the peel force from the adhered object meet the above-mentioned numerical range, the protective film can be easily peeled off from the optical laminate with the protective film and the polarizing plate with the protective film, which is preferred in terms of improving the operability of the sample.

[0240] The optical laminate with protective film and the polarizing plate with protective film of the present invention are made by peeling off their protective film to form a polarizing plate having a polarizing film and the aforementioned optical laminate, thereby making them applicable to a wide variety of display devices.

[0241] A display device is a device having display elements, including light-emitting elements or light-emitting devices as light sources. Examples of display devices include liquid crystal display devices, organic electroluminescent (EL) display devices, inorganic electroluminescent (EL) display devices, touch panel display devices, electron emission display devices (e.g., field emission display devices (FED), surface electric field emission display devices (SED)), electronic paper (display devices using electronic ink, electrophoretic elements, plasma display devices, projection display devices (e.g., grating light valve (GLV) display devices, display devices with digital micromirror devices (DMD)), and piezoelectric ceramic displays, etc. Liquid crystal display devices include any one of transmissive liquid crystal display devices, semi-transmissive liquid crystal display devices, reflective liquid crystal display devices, direct-viewing liquid crystal display devices, and projection liquid crystal display devices. In particular, considering the ease with which the effects of the laminate and polarizing plate of the present invention can be significantly achieved, they can be suitably used in liquid crystal display devices, and are particularly preferred as IPS (in-plane) displays. (Switching) Liquid crystal display device applications. By using the polarizing plate of the present invention, it is easy to achieve a thinner display device, and a display device capable of exhibiting the following characteristics can be obtained: prevention of light leakage and color shift when visually recognizing the liquid crystal display device from an oblique direction when displaying black.

[0242] Example The present invention will now be described in more detail with reference to the embodiments. It should be noted that, unless otherwise specified, "%" and "parts" in the examples refer to mass percentage and mass parts, respectively. Furthermore, the apparatus and measurement methods used in the following embodiments are described below.

[0243] • The in-plane phase difference values ​​R (550), R40 (450) and R40 (550) at a wavelength of 550 nm were measured using a phase difference measuring device (manufactured by Oji Measurement Equipment Co., Ltd., KOBRA-WPR).

[0244] • Film thickness was measured using an ellipsometer M-220 manufactured by Japan Spectrophotometer Co., Ltd.

[0245] [Preparation of compositions 1-3 for forming optical anisotropic films] Add 0.2 parts of a leveling agent (BYK333; manufactured by BYK-Chemie) and 6 parts of a polymerization initiator 2-dimethylamino-2-benzyl-1-(4-morpholinophenyl)-1-butanone (Irgacure 369 (Irg369); manufactured by BASF JAPAN) and 8 parts of dipentaerythritol hexaacrylate (DPHA; manufactured by Tokyo Chemical Co., Ltd.) to 100 parts of a mixture of polymerizable liquid crystal compound A, polymerizable liquid crystal compound B and polymerizable liquid crystal compound C described below.

[0246] Furthermore, cyclopentanone as a solvent was added to achieve a solid component concentration of 12%, and the mixture was stirred at 50°C for 1 hour to obtain a composition for forming an optically anisotropic film. It should be noted that the mixing ratio of polymerizable liquid crystal compound A, polymerizable liquid crystal compound B, and polymerizable liquid crystal compound C was adjusted according to the target R40 (450) / R40 (550) as described in Table 1, and the names of each composition are listed in Table 1.

[0247] The ratios of polymeric liquid crystal compounds A, B, and C in Table 1 are set as parts relative to 100 parts of the total amount of polymeric liquid crystal compounds.

[0248] [Table 1] Polymerizable liquid crystal compound A was manufactured using the method described in Japanese Patent Application Publication No. 2022-120659. Polymerizable liquid crystal compound B was manufactured using the method described in Japanese Patent Application Publication No. 2010-31223. Furthermore, polymerizable liquid crystal compound C was manufactured using the method described in Japanese Patent Application Publication No. 2009-173893. The molecular structures of each compound are shown below.

[0249] Polymerizable liquid crystal compound A: [Chemical Formula 7] Polymerizable liquid crystal compound B: [Chemical Formula 8] Polymerizable liquid crystal compound C: [Chemical Formula 9] (Example 1) Referring to Japanese Patent Application Publication No. 2008-281667, a strip-shaped film with a thickness of 54 μm was obtained by longitudinally uniaxially stretching a resin film obtained by hydrogenating a ring-opening polymer of norbornene monomers as a second optical anisotropy layer 1. The in-plane phase difference of this film at a wavelength of 550 nm is 127 nm. The surface of the film was plasma-treated using an atmospheric pressure plasma apparatus (manufactured by Sekisui Chemicals Co., Ltd.) while being transported at a linear speed of 15 m / min. Then, the optical anisotropy layer forming composition 1 was coated using a die coater, dried at 90°C for 1 minute, and then irradiated from the coated surface with ultraviolet light (cumulative light intensity at a wavelength of 365 nm: 500 mJ / cm² under nitrogen atmosphere) using a high-pressure mercury lamp (manufactured by EYE GRAPHICS COMPANY). 2 This forms the first optical anisotropic layer 1, resulting in a long strip-shaped optical laminate 1.

[0250] It should be noted that the optical anisotropic layer forming composition 1 was coated on a glass substrate with a phase difference value of almost 0 to form the same first optical anisotropic layer 1 as described above. Its optical properties were measured, and the in-plane phase difference value was 0.3 nm, R'40 (550) was 18 nm, the film thickness was 1.0 μm, and R'40 (450) / R'40 (550) was 1.00.

[0251] Furthermore, based on the in-plane phase difference value of the first optical anisotropic layer 1 relative to light with a wavelength of 550 nm, the phase difference value R'40 (550) obtained by measuring with the fast axis as the tilt center and the sample tilted at 40°, the average refractive index (1.58) and the film thickness, the values ​​of each principal refractive index in the refractive index ellipsoid formed by the first optical anisotropic layer 1 were calculated using three-dimensional refractive index calculation software (manufactured by Oji Measurement Machinery Co., Ltd., N-CALC), and it was confirmed that it satisfies equation (1).

[0252] In addition, the R40 (550) of optical laminate 1 is 131 nm.

[0253] The obtained elongated optical laminate 1 and a protective film 1, which is obtained by laminating a (meth)acrylic adhesive layer (thickness: 15 μm) onto an elongated biaxially stretched polyethylene terephthalate (thickness: 38 μm), are continuously transported and stacked. These are then passed between a pair of bonding rollers, thereby pushing the laminate of the protective film 1 and the optical laminate 1 from above and below, continuously producing an elongated optical laminate 1 with a protective film. The protective film 1 is bonded to the side of the second optical anisotropic layer 1 of the optical laminate opposite to the side of the first optical anisotropic layer. The resulting elongated optical laminate 1 with a protective film is stored at room temperature in a wound state for 3 months. Although changes in appearance were observed, it was able to be stored stably. For the results of storing the wound body at room temperature for 3 months, cases with no problems and no confirmed changes in appearance are marked as ◎; cases with no problems but confirmed changes in appearance are marked as 〇; and cases with problems are marked as ×. The results are shown in Tables 2 and 3.

[0254] <Determination of Tensile Modulus> Test samples with a long side of 100 mm and a short side of 50 mm were cut from the individual optical laminate 1 or protective film 1. Following JIS K7161:1994 and JIS K7127:1999, the test samples were clamped at both ends of the long side using the upper and lower clamps of a tensile testing machine (Autograph AG-1S testing machine manufactured by Shimadzu Corporation) with a clamping interval of 5 cm. The test samples were stretched along the long side at a tensile speed of 10 mm / min at an environment of 23°C and 55% RH. The tensile modulus of elasticity (MPa) along the long side at 23°C and 55% RH was calculated. Here, the tensile modulus of elasticity when the long side is parallel to the MD direction (transport direction) of the optical laminate 1 or the protective film 1 is denoted as E1 or E2, respectively. The tensile modulus of elasticity when the short side is parallel to the MD direction (transport direction) of the optical laminate 1 or the protective film 1, i.e., when the long side is parallel to the TD direction (width direction), is denoted as E3 or E4, respectively. It should be noted that 3 to 5 samples were evaluated for each sample, and the average value was used. The results are shown in Tables 2 and 3.

[0255] <Determination of the peel strength of the protective film> A 150mm × 25mm sample was cut from the obtained elongated optical laminate 1 with the MD direction as the long side. In the cut sample, a 5μm thick adhesive-coated release film was bonded to the side opposite to the second anisotropic layer of the first optical layer. The release film was peeled off, exposing the adhesive layer, which was then bonded to the center of an alkali-free glass substrate (Corning Corporation, Eagle XG) measuring 160mm in length, 50mm in width, and 0.7mm in thickness. The resulting test piece (the optical laminate with protective film attached to the glass substrate) was then placed in an autoclave at 50°C and 5kgf / cm² pressure. 2 The sample was pressurized at 490.3 kPa for 20 minutes and used as the test sample. Then, it was stored at 23°C and 55% relative humidity for 30 minutes.

[0256] Next, the cutting blade was inserted between the protective film and the optical laminate of the protective film-coated optical laminate, and a 30mm peel was performed along the length direction from the end. The peeled portion was clamped using the clamping part of a universal tensile testing machine (Shimadzu Corporation, AGS-50NX). The test piece in this state was subjected to a 180-degree peel test in an atmosphere of 23°C and 55% relative humidity according to JISK6854-2:1999 (Adhesives - Test method for peel bond strength - Part 2: 180-degree peel) at a clamping speed of 300mm / min. The average peel force over a length of 120mm excluding the 30mm clamping part was determined. Cases where the protective film could be easily peeled from the optical anisotropic layer with a protective film were marked as ◎; cases where peeling was possible without problems were marked as 〇; and cases where peeling was difficult due to high peel force were marked as ×. The results are shown in Tables 2 and 3.

[0257] <Manufacturing of Polarizing Film> A polyvinyl alcohol (PVA) film with an average degree of polymerization of approximately 2,400, a saponification degree of ≥99.9 mol%, and a thickness of 75 μm was immersed in pure water at 30°C, and then immersed in an aqueous solution of iodine / potassium iodide / water at 30°C for iodine staining (iodine staining step). The PVA film after the iodine staining step was then immersed in an aqueous solution of potassium iodide / boric acid / water at 56.5°C for boric acid treatment (boric acid treatment step). The PVA film after the boric acid treatment step was washed with pure water at 8°C and then dried at 65°C to obtain a polarizing film with iodine adsorbed and oriented on the PVA (stretched thickness 27 μm). Stretching was performed during the iodine staining and boric acid treatment steps. The total stretching ratio was 5.3 times. A polarizing film was bonded to a saponified cellulose triacetate film (Konica Minolta KC4UYTAC 40μm) using a holding roller via an aqueous adhesive. The resulting composite was dried at 60°C for 2 minutes while maintaining a tension of 430 N / m, resulting in a polarizing film with a cellulose triacetate film as a protective film on one side. It should be noted that the aforementioned aqueous adhesive was prepared by adding 3 parts of carboxyl-modified polyvinyl alcohol (Kuraray Poval KL318) and 1.5 parts of water-soluble polyamide epoxy resin (Sumirez Resin 650, 30% solids concentration aqueous solution, Sumika Chemtex Company) to 100 parts of water.

[0258] Using the polarizing surface of the obtained polarizing film as the incident surface, the optical properties were measured using a spectrophotometer (manufactured by Japan Spectrophotometer Co., Ltd., V7100). The results showed that the transmittance of the visible correction element was 42.1%, and the polarization degree of the visible correction element was 99.996%.

[0259] After corona treatment is applied to the side of the first optical anisotropic layer of the obtained optical laminate 1 that is opposite to the second optical anisotropic layer, the corona-treated side of the optical anisotropic layer 1 is bonded to the obtained polarizing film 1 through an acrylic pressure-sensitive adhesive (manufactured by Lintec Corporation) with a thickness of 15 μm, thereby obtaining the polarizing plate 1 with a protective film.

[0260] <Confirmation of oblique hue> After peeling off the protective film from the obtained polarizing plate 1, the polarizing plate was adhered to the backlight using adhesive. It was then visually observed from a distance of 50cm in a direction ranging from 0° to 360° (elevation angle 60°) to confirm the oblique hue. Extremely clear black was marked with ◎; clear black with 〇; slight light leakage with △; and light leakage with ×. The results are shown in Tables 2 and 3.

[0261] (Example 2) Protective film 1 was replaced with protective film 2, which consisted of a (meth)acrylic adhesive layer (thickness: 15 μm) laminated on biaxially stretched polyethylene terephthalate (thickness: 75 μm). Protective film 2 was then bonded to the side of the second optical anisotropy layer of the optical laminate opposite to the first optical anisotropy layer via the adhesive layer. All other things being done in the same manner as in Example 1, an optical laminate 2 with a protective film was obtained. The strip-shaped optical laminate 2 with a protective film was stored at room temperature for 3 months in a wound state, and no significant changes were observed, indicating stable preservation. Furthermore, except for using the obtained optical laminate 2 with a protective film, a polarizing plate 2 with a protective film was obtained in the same manner as in Example 1. The results are shown in Tables 2 and 3.

[0262] (Example 3) Five parts by mass of an addition-reactive silicone (manufactured by Dow Corning Toray Co., Ltd., SRX-345), 0.5 parts by mass of Li(CF3SO2)2N, 95 parts by mass of a 1:1 mixed solvent of toluene and ethyl acetate, and 0.05 parts by mass of a platinum catalyst (manufactured by Dow Corning Toray Co., Ltd., SRX-212 Catalyst) were mixed and stirred to prepare a coating to form a release agent layer. Next, the coating to form the release agent layer was applied to the surface of biaxially stretched polyethylene terephthalate (38 μm) to a dried thickness of 0.2 μm, and dried in a hot air circulating oven at 120°C for 1 minute. A (meth)acrylic adhesive layer (15 μm) was then laminated onto the polyethylene terephthalate surface opposite to the side where the release layer was formed, forming a protective film 3. Next, the obtained protective film 3 was bonded to the surface of the second optical anisotropic layer of the optical laminate opposite to the first optical anisotropic layer via the adhesive layer. This process was repeated in the same manner as in Example 1, resulting in an optical laminate 3 with a protective film. The strip-shaped optical laminate 3 with the protective film was stored at room temperature for 3 months in a wound state, and no significant changes were observed, indicating stable preservation. Furthermore, except for using the obtained optical laminate 3 with the protective film, the process was repeated in the same manner as in Example 1 to obtain a polarizing plate 3 with a protective film. The results are shown in Tables 2 and 3.

[0263] (Example 4) Except that the thickness of the release layer formed in Example 3 was set to 0.4 μm, the same procedure was followed to manufacture a protective film 4. The protective film 4 was then bonded to the side of the second optical anisotropic layer of the optical laminate opposite to the first optical anisotropic layer via the aforementioned adhesive layer. Otherwise, the procedure was followed in the same manner as in Example 1 to obtain an optical laminate 4 with a protective film. The strip-shaped optical laminate 4 with a protective film was stored at room temperature for 3 months in a wound state, and no significant changes were observed, indicating stable preservation. Furthermore, except that the obtained optical laminate 4 with a protective film was used, the procedure was followed in the same manner as in Example 1 to obtain a polarizing plate 4 with a protective film. The results are shown in Tables 2 and 3.

[0264] (Example 5) Referring to Japanese Patent Application Publication No. 2008-281667, a 54 μm thick elongated film obtained by longitudinally uniaxially stretching a resin film obtained by hydrogenating a ring-opening polymer of norbornene monomers was used as the second optical anisotropy layer 2. The in-plane phase difference of this film at a wavelength of 550 nm was 160 nm. Using the obtained second optical anisotropy layer 2, the thickness of the first optical anisotropy layer 1 was set to 1.7 μm, and the same procedure as in Example 1 was performed to obtain an optical laminate 5 with a protective film. The elongated optical laminate 5 with a protective film was stored at room temperature in a wound state for 3 months. Although changes in appearance were observed, it could be stably preserved. In addition, except for using the obtained optical laminate 5 with a protective film, the same procedure as in Example 1 was performed to obtain a polarizing plate 5 with a protective film. The results are shown in Tables 2 and 3.

[0265] (Example 6) Referring to Japanese Patent Application Publication No. 2008-281667, a 54 μm thick elongated film obtained by longitudinally uniaxially stretching a resin film formed by hydrogenating a ring-opening polymer of norbornene monomers was used as the second optical anisotropy layer 3. The in-plane phase difference of this film at a wavelength of 550 nm was 117 nm. Using the obtained second optical anisotropy layer 3, the thickness of the first optical anisotropy layer 1 was set to 0.3 μm, and the same procedure as in Example 1 was performed to obtain an optical laminate 6 with a protective film. The elongated optical laminate 6 with a protective film was stored at room temperature in a wound state for 3 months. Although changes in appearance were observed, it could be stably preserved. In addition, except for using the obtained optical laminate 6 with a protective film, the same procedure as in Example 1 was performed to obtain a polarizing plate 6 with a protective film. The results are shown in Tables 2 and 3.

[0266] (Example 7) The first optical anisotropic layer 2 is formed by coating the optical anisotropic layer forming composition 2, and otherwise the same procedure as in Example 1 is performed to obtain an optical laminate 7 with a protective film.

[0267] The optical properties of the obtained first optical anisotropic layer 2 were measured in the same manner as in Example 1. The results showed that R'40 (550) was 10 nm, the film thickness was 1.0 μm, and R'40 (450) / R'40 (550) was 0.85. This confirmed that the values ​​of each principal refractive index in the refractive index ellipsoid formed by the first optical anisotropic layer 2 satisfied Equation (1).

[0268] Furthermore, the long strip-shaped optical laminate 7 with a protective film was stored at room temperature for 3 months in a wound state. Although changes in appearance were observed, it was able to be stored stably. In addition, except for using the obtained optical laminate 7 with a protective film, the same procedure as in Example 1 was performed to obtain a polarizing plate 7 with a protective film. The results are shown in Tables 2 and 3.

[0269] (Example 8) The first optical anisotropic layer 3 is formed by coating the optical anisotropic layer forming composition 3, and otherwise the same procedure as in Example 1 is performed to obtain an optical laminate 8 with a protective film.

[0270] The optical properties of the obtained first optical anisotropic layer 3 were measured in the same manner as in Example 1. The results showed that R'40 (550) was 22 nm, the film thickness was 1.0 μm, and R'40 (450) / R'40 (550) was 1.05. This confirmed that the values ​​of each principal refractive index in the refractive index ellipsoid formed by the first optical anisotropic layer 3 satisfied Equation (1).

[0271] Furthermore, the long strip-shaped optical laminate 8 with a protective film was stored at room temperature for 3 months in a wound state. Although changes in appearance were observed, it was able to be stored stably. In addition, except for using the obtained optical laminate 8 with a protective film, the same procedure as in Example 1 was performed to obtain a polarizing plate 8 with a protective film. The results are shown in Tables 2 and 3.

[0272] (Example 9) The protective film 1 was replaced with a strip-shaped biaxially stretched polyethylene (thickness: 25 μm) protective film 5. The protective film 5 was adhered to the surface of the second optical anisotropic layer of the optical laminate opposite to the first optical anisotropic layer. Otherwise, the process was the same as in Example 1, resulting in an optical laminate 9 with a protective film. The strip-shaped optical laminate 9 with the protective film was stored at room temperature for 3 months in a wound state. Although changes in appearance were observed, it was able to be stored stably. Furthermore, except for using the obtained optical laminate 9 with the protective film, the process was the same as in Example 1, resulting in a polarizing plate 9 with a protective film. The results are shown in Tables 2 and 3.

[0273] (Comparative Example 1) After obtaining the long strip-shaped optical laminate 1 in the same manner as in Example 1, it was stored at room temperature for 3 months in a wound state without attaching a protective film. The results showed that adhesion occurred and it could not be stored stably.

[0274] (Comparative Example 2) A composition for forming a hard coating is prepared by mixing the following components: PET30 (97.0 parts by weight), photopolymerization initiator Irgacure 907 (3.0 parts by weight, manufactured by BASF), and methyl ethyl ketone (81.8 parts by weight). Here, PET30 is a mixture of pentaerythritol tetraacrylate and pentaerythritol triacrylate (manufactured by Nippon Kayaku Co., Ltd.).

[0275] Next, the substrate film (acylated cellulose film TD40, manufactured by FUJIFILM Corporation, 1,340 mm wide and 40 μm thick), already wound into a roll, was unwound. The aforementioned hard coating composition was applied using a slit-die die coating method at a transport speed of 30 m / min, and dried at 60°C for 150 seconds to form a coating layer. Then, under a nitrogen atmosphere and an oxygen concentration of approximately 0.1%, the film was irradiated with an illuminance of 400 mW / cm² using an air-cooled metal halide lamp (manufactured by EYE GRAPHICS COMPANY) with an output power of 160 W / cm². 2 The irradiation dose was 120 mJ / cm. 2The coating layer was cured by ultraviolet light to form an HC layer. The coating thickness of the coating layer was adjusted to make the film thickness of the HC layer 7 μm. In this way, a second optical anisotropic layer having an HC layer on one side of the substrate film was obtained. After plasma treatment of the side of the hard coating layer in the obtained second optical anisotropic layer opposite to the acylated cellulose film, the optical anisotropic layer forming composition 1 was coated on the plasma-treated side, thereby forming a first optical anisotropic layer 1 on the hard coating layer, and obtaining a strip-shaped optical laminate 10. Next, the protective film 5 described in Example 9 was attached to the surface of the acylated cellulose film in the second optical anisotropic layer of the optical laminate, and the process was carried out in the same manner as in Example 9, to obtain an optical laminate 10 with a protective film. In addition, except for using the obtained optical laminate 10 with a protective film, the process was carried out in the same manner as in Example 1, to obtain a polarizing plate 10 with a protective film. The results are shown in Tables 2 and 3.

[0276] (Comparative Example 3) The thickness of the first optical anisotropic layer 1 was set to 1.9 μm, and the process was carried out in the same manner as in Example 5 to obtain an optical laminate 11 with a protective film. Furthermore, except for using the obtained optical laminate 11 with a protective film, the process was carried out in the same manner as in Example 1 to obtain a polarizing plate 11 with a protective film. The results are shown in Tables 2 and 3.

[0277] (Comparative Example 4) In Example 1, an optical laminate 12 with a protective film was obtained by bonding a protective film 1 onto the second optical anisotropic layer 1 without forming a first optical anisotropic layer 1. Furthermore, except for using the obtained optical laminate 12 with a protective film, the same procedure as in Example 1 was followed to obtain a polarizing plate 12 with a protective film. The results are shown in Tables 2 and 3.

[0278] [Table 2] [Table 3] According to the present invention, an optical laminate with a protective film is provided, which reduces light leakage when visually recognizing from an oblique direction and maintains excellent stability; a polarizing plate with a protective film is provided; and an image display device having a polarizing plate having a polarizing film and the aforementioned optical laminate is provided.

Claims

1. An optical laminate with a protective film, comprising a protective film and an optical laminate having a first optical anisotropy layer and a second optical anisotropy layer, wherein, The R40(550) of the optical laminate satisfies 110nm ≤ R40(550) ≤ 175nm. The ratio of the tensile elastic modulus E1 of the optical laminate in the direction parallel to the MD direction to the tensile elastic modulus E2 of the protective film in the direction parallel to the MD direction satisfies E1 / E2 < 10. R40 (550) represents the phase difference when the optical stack is tilted by 40 degrees with the axis parallel to the fast axis in the plane of the optical stack as the tilt center axis at a wavelength of 550 nm.

2. The optical laminate with a protective film as described in claim 1, wherein, The thickness of the first optical anisotropic layer is greater than 0.1 μm and less than 3.0 μm.

3. The optical laminate with a protective film as described in claim 1, wherein, The first optical anisotropic layer satisfies the following equation (1). nx≈ny<nz (1) In equation (1), nx represents the principal refractive index in the direction parallel to the film plane in the refractive index ellipsoid formed by the optical anisotropic layer; ny represents the principal refractive index in the direction parallel to the film plane and orthogonal to the direction of nx in the refractive index ellipsoid formed by the optical anisotropic layer; nz represents the principal refractive index in the direction perpendicular to the film plane in the refractive index ellipsoid formed by the optical anisotropic layer; where nx, ny and nz each represent the principal refractive index relative to light with a wavelength of 550 nm.

4. The optical laminate with a protective film as described in claim 1, wherein, The first optical anisotropic layer satisfies the following equation (2). 5nm≤R'40(550)≤30nm (2) In equation (2), R'40 (550) represents the phase difference when the first optical anisotropic layer is tilted by 40 degrees at a wavelength of 550 nm.

5. The optical laminate with a protective film as described in claim 1, wherein, The first optical anisotropic layer satisfies the following equation (3). R'40 (450) / R'40 (550) ≤ 1.04 (3) In equation (3), R'40 (450) represents the phase difference when the first optical anisotropic layer is tilted by 40 degrees at a wavelength of 450 nm, and R'40 (550) represents the phase difference when the first optical anisotropic layer is tilted by 40 degrees at a wavelength of 550 nm.

6. A polarizing plate with a protective film, comprising a polarizing film and an optical laminate with a protective film according to any one of claims 1 to 5.

7. A polarizing plate comprising the polarizing film and the optical laminate of the polarizing plate with protective film as described in claim 6.

8. An image display device comprising the polarizing plate of claim 7.

Citation Information

Patent Citations

  • Method for producing retardation film

    JP2008281667A

  • Liquid crystal panel and liquid crystal display

    JP2009139747A

  • Compound, optical film, and manufacturing method for optical film

    JP2009173893A

  • Compound, optical film, and method for producing optical film

    JP2010031223A

  • compound

    JP2010270108A